Method for decomposing plastic-containing materials, method for recovering inorganic materials, recycled carbon fiber and method for manufacturing recycled carbon fiber, blended yarn, carbon fiber reinforced thermoplastic resin pellets containing the blended yarn and method for manufacturing the same, carbon fiber reinforced thermoplastic resin strand and method for manufacturing the same, and carbon fiber reinforced thermoplastic pellets
Patent Information
- Application Number
- JP2022546929
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-09-01
- Filing Date
- 2021-08-31
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2041-08-31
AI Technical Summary
【0046】 (第1の本発明) 本開示に係る第1の発明によれば、プラスチック含有材料を安定的にかつ効率的に分解することができるプラスチック含有材料の分解方法を提供することができる。
Smart Images

Figure 0007634546000006 
Figure 0007634546000007 
Figure 0007634546000008
Abstract
Description
[Technical field]
[0001] (First invention) The first invention of the present disclosure (the first present invention) relates to a method for decomposing plastic-containing materials, a method for recovering inorganic fibers that includes this decomposition method, recycled carbon fibers, and a method for producing recycled carbon fibers.
[0002] (Second Invention) The second invention of the present disclosure relates to a blended yarn of recycled carbon fiber and thermoplastic resin fiber, and a carbon fiber reinforced thermoplastic resin pellet formed from the blended yarn. The second invention of the present disclosure also relates to a manufacturing method thereof.
[0003] (Third Invention) The third invention of the present disclosure relates to a carbon fiber reinforced thermoplastic resin strand containing a blended yarn of recycled carbon fiber and thermoplastic resin fiber, suitable for three-dimensional modeling. The third invention of the present disclosure also relates to a manufacturing method thereof.
[0004] (Fourth Invention) A fourth aspect of the present disclosure (the fourth present invention) relates to carbon fiber reinforced thermoplastic resin pellets containing recycled carbon fibers produced using waste materials of carbon fiber reinforced resin moldings or the like. [Background technology]
[0005] (Regarding the first invention) A method utilizing thermal activation of semiconductors (TASC method) is known as a method for decomposing plastics or recovering reinforcing fibers from fiber-reinforced plastics.
[0006] Patent Document 1 describes that a material to be decomposed, such as polycarbonate, is heated in air in the presence of a semiconductor powder, such as titanium dioxide.
[0007] Patent Document 2 discloses a method for recovering glass fibers from fiber-reinforced plastics. This document also describes the use of Cr as a semiconductor powder. 2 O3 The article describes how the glass fibers were recovered by heating the mixture and fiber-reinforced plastic in an oven.
[0008] Patent Document 3 describes a method for treating plastic or plastic composite materials. This method involves contacting a semiconductor only with the surface of the plastic or plastic composite material to be treated, and heating the material to be treated in the presence of oxygen. This document describes treating the material to be treated by placing it on a substrate having a semiconductor supported on the surface of a porous body (e.g., a honeycomb support) made of ceramics or the like.
[0009] Patent Document 4 discloses a method for decomposing a plastic composite material. The method includes contacting the plastic composite material with a catalyst of an inorganic oxide having a band gap of 4 eV or less in a reaction vessel. The document describes a honeycomb-type denitration catalyst (TiO 2 / V 2 O 5 / WO 3 Or MoO 3 The paper describes that the plastic composite material was heat-treated under dry air using a catalyst such as a three-way catalyst (such as a 3-way catalyst). The paper also describes that the surface temperature of the plastic composite material was set to 480 to 650°C.
[0010] As a method for recovering carbon fibers from carbon fiber-containing plastics and the like, the following pyrolysis method is also known (Patent Documents 5 to 7).
[0011] Patent Document 5 discloses a method for producing recycled carbon fibers using carbon fiber reinforced plastic as a raw material. The method described in this document includes a step of dry distilling the carbon fiber reinforced plastic to adhere fixed carbon to the surface of the carbon fiber, and a step of removing a part of the fixed carbon by heating to obtain recycled carbon fibers.
[0012] Patent Document 6 discloses a method for obtaining a carbon fiber substrate as a recycled carbon fiber bundle from a carbon fiber reinforced resin. This method includes obtaining a heat-treated product by thermally decomposing the matrix resin by heating the carbon fiber reinforced resin, and crushing the heat-treated product.
[0013] Patent document 7 discloses a method for recovering carbon fibers from a carbon fiber-containing resin. The method includes subjecting an object having a carbon fiber-containing resin to multiple stages of pyrolysis under a specific range of oxygen concentrations. In the method, the object passes through a first pyrolysis zone B1, which is carried out at a predetermined temperature T(B1) and a predetermined oxygen content G(B1), followed by a second pyrolysis zone B2, which is carried out at a predetermined temperature T(B2) and a predetermined oxygen content G(B2). The oxygen content G(B2) is higher than the oxygen content G(B1), and the temperature T(B2) is higher than the temperature T(B1).
[0014] (Regarding the second invention) Carbon fiber has excellent specific strength and specific elastic modulus, and is lightweight, so it is used as a reinforcing fiber for thermoplastic resins. Carbon fiber reinforced plastic composite materials (also called carbon fiber reinforced plastics, CFRP) are used in a wide range of applications, including sports and general industrial applications, as well as aerospace and automotive applications.
[0015] Carbon fiber reinforced thermoplastic resin pellets are one form of carbon fiber reinforced resin composite material. There are two types of carbon fiber reinforced thermoplastic resin pellets: long fiber reinforced pellets, which are produced by cutting a resin strand in which continuous carbon fibers are coated with a thermoplastic resin, and short fiber reinforced pellets, which are produced by cutting a resin strand in which discontinuous carbon fibers are kneaded and dispersed in a thermoplastic resin. Since long fiber reinforced pellets contain carbon fibers with a relatively long fiber length compared to short fiber reinforced pellets, they can be fed to an injection molding machine or the like to produce a carbon fiber-containing product with excellent mechanical properties.
[0016] In recent years, there has been an increasing demand for recycled carbon fibers recovered from used carbon fiber-containing products. Most recycled carbon fibers are discontinuously cut carbon fibers, and methods for producing spun yarn from recycled carbon fibers have been investigated in order to treat them in the same way as unused continuous carbon fibers as a raw material for carbon fiber-containing products such as carbon fiber reinforced resin composite materials.
[0017] Patent Document 8 describes a method for producing a spun yarn by blending a charcoal containing recycled carbon fibers obtained by heat treating scraps of carbon fiber reinforced resin composite material at a temperature of 900°C or higher with thermoplastic resin fibers.
[0018] Patent Document 9 describes a method for utilizing spun yarn made by blending cut unused discontinuous carbon fibers with synthetic fibers, imitating recycled carbon fibers that do not contain carbides, rather than the recycled carbon fibers recovered by heat treatment of carbon fiber reinforced resin composite materials.
[0019] Patent Document 10 describes a method for producing spun yarn using only carbon fibers or recycled carbon fibers without blending with thermoplastic fibers.
[0020] (Regarding the third invention) Conventionally, a technology has been known in which a 3D model is generated by sequentially stacking resin on each cross section of an object cut along multiple parallel planes. This technology is called 3D modeling and can be used for prototyping parts and manufacturing products. Known 3D modeling methods include the stereolithography method using photocurable resin, the powder lamination method using metal or resin powder, the fused deposition method in which resin is melted and deposited, the thin plate lamination method in which paper, resin sheets, or thin metal plates are laminated, and the inkjet method in which liquid or powdered resin or metal is sprayed.
[0021] As an example of the fused deposition method, Patent Document 11 discloses a fused deposition method using a thermoplastic polymer material. In this technique, a solid thermoplastic polymer material is supplied to a discharge head, the polymer material is melted in the discharge head, the molten polymer material is discharged from the discharge head, and the layer-like deposition is repeated. Examples of thermoplastic polymers that can be used in this technique include polyethersulfone, polyetherimide, polyphenylsulfone, polyphenylene, polycarbonate, high-impact polystyrene, polysulfone, polystyrene, acrylic resin, amorphous polyamide, polyester, nylon, PEEK, and ABS. In particular, this method is suitable for use with polylactic acid, a thermoplastic polyester derived from plants, because it can be melted and discharged at a relatively low temperature and has the advantage of being environmentally friendly.
[0022] Furthermore, fiber-reinforced resin compositions (FRP molded products) in which fibers are incorporated into resin are lightweight and have excellent mechanical properties, and are therefore used in a wide range of fields, from aerospace applications to sports applications, and a technique is also known in which, in the above-mentioned melt lamination method, a fiber-resin material in which molten thermoplastic resin and fibers are integrated is laminated onto a mold material, and then another fiber-resin material is laminated onto the laminated fiber-resin material (Patent Document 12).
[0023] Furthermore, as mentioned above, in recent years, there has been an increasing demand for recycled carbon fibers recovered from used carbon fiber-containing products, etc. Most recycled carbon fibers are discontinuously cut carbon fibers, and in order to handle them in the same way as unused continuous carbon fibers as a raw material for carbon fiber-containing products such as carbon fiber reinforced resin composite materials, methods for producing spun yarn from recycled carbon fibers have been studied (see Patent Documents 8 to 10 above).
[0024] (Regarding the fourth invention) As mentioned above, carbon fiber has excellent specific strength and specific elastic modulus, and is lightweight, so it is used as a reinforcing fiber for thermoplastic resins. Carbon fiber reinforced plastic composite materials (also called carbon fiber reinforced plastics, CFRP) are used in a wide range of applications, including sports and general industrial applications, as well as aerospace and automotive applications.
[0025] As described above, one form of carbon fiber reinforced resin composite material is carbon fiber reinforced thermoplastic resin pellets. There are two types of carbon fiber reinforced thermoplastic resin pellets: long fiber reinforced pellets produced by cutting a resin strand in which continuous carbon fibers are coated with a thermoplastic resin, and short fiber reinforced pellets produced by cutting a resin strand in which discontinuous carbon fibers are kneaded and dispersed in a thermoplastic resin. Although short fiber reinforced thermoplastic resin pellets have inferior mechanical properties to long fiber reinforced thermoplastic resin pellets, they are widely adopted as a method for producing them at low cost.
[0026] Patent Documents 13 and 14 describe a method for producing a composite containing recycled carbon fibers by melt kneading carbon fibers. The carbon fibers used in this method are recovered from waste carbon fiber reinforced resin composite materials by pyrolysis, and have residual carbon attached to them, which is the carbonized matrix component.
[0027] Patent Document 15 describes a carbon fiber aggregate having improved feedability by adding a fiber treatment agent to recycled carbon fibers recovered from carbon fiber reinforced composite materials and forming the fibers into a cylindrical shape using an extrusion granulator. [Prior art documents] [Patent documents]
[0028] [Patent Document 1] JP 2005-139440 A [Patent Document 2] JP 2012-211223 A [Patent Document 3] JP 2013-146649 A [Patent Document 4] JP 2020-28850 A [Patent Document 5] JP 2013-64219 A [Patent Document 6] International Publication No. 2018 / 212016 [Patent Document 7] JP 2018-109184 A [Patent Document 8] JP 2018-35492 A [Patent Document 9] JP 2018-123438 A [Patent Document 10] JP 2020-90738 A [Patent Document 11] Special Publication No. 2005-531439 [Patent Document 12] Special Publication No. 2016-520459 [Patent Document 13] JP 2020-49820 A [Patent Document 14] JP 2019-155634 A [Patent Document 15] Patent Publication No. 2021-55198 Summary of the Invention [Problem to be solved by the invention]
[0029] (First aspect of the present invention) Conventional plastic decomposition methods involve heat treatment at relatively high temperatures, which can result in excessive energy consumption.
[0030] Furthermore, in conventional plastic decomposition methods that use the thermal activation of semiconductors, there is a risk of excessive oxidation heat generation during heat treatment in the atmosphere. When excessive oxidation heat generation occurs, it becomes difficult to accurately control the temperature, and therefore the method may be unsuitable in terms of processing stability, particularly on an industrial scale.
[0031] Furthermore, when the oxygen concentration is controlled to a relatively low concentration, conventional pyrolysis methods that do not use semiconductors may result in insufficient plastic decomposition efficiency or reduced physical properties of the recovered carbon fibers.
[0032] In this background, the first invention of the present disclosure aims to provide a method for decomposing plastic-containing materials that can stably and efficiently decompose plastic-containing materials, and a method for recovering inorganic materials.
[0033] (Second Invention) Methods for decomposing used carbon fiber reinforced resin composite materials to obtain recycled carbon fibers include a method of decomposing the resin components by heat treatment, a method of dissolving and removing the resin components using a solvent, and a method of electrolysis. The method that has been widely used up to now is the method of decomposing the resin components by heat treatment.
[0034] However, there have been cases where it has not been possible to produce a blended yarn with thermoplastic resin fibers using recycled carbon fibers obtained by the method of decomposing the carbon fibers through heat treatment as a raw material.
[0035] The second invention of the present disclosure also aims to provide a blended yarn with thermoplastic resin fiber, which is stably produced using recycled carbon fiber obtained by a method of decomposing the recycled carbon fiber through heat treatment as a raw material, and to provide a carbon fiber-reinforced thermoplastic resin fiber pellet formed from the blended yarn.
[0036] (The Third Invention) Methods for decomposing used carbon fiber reinforced resin composite materials to obtain recycled carbon fibers include a method of decomposing the resin components by heat treatment, a method of dissolving and removing the resin components using a solvent, and a method of electrolysis. The method that has been widely used up to now is the method of decomposing the resin components by heat treatment.
[0037] However, when recycled carbon fibers obtained by the method of decomposing by heat treatment are used as a raw material to produce a blended yarn with thermoplastic resin fibers, there are problems in that the resin in the carbon fiber reinforced resin composite material does not decompose completely, residual char is generated, making it difficult to produce the blended yarn, and the mechanical properties of the fiber obtained after decomposition, particularly the strength of the fiber, are reduced compared to the fiber before decomposition, and the strength of the molded product of the fiber reinforced composite material using this fiber is also reduced.
[0038] An object of the third invention of the present disclosure is to provide a carbon fiber reinforced thermoplastic resin strand that can be stably produced using recycled carbon fiber obtained by a method of decomposing the carbon fiber through heat treatment and a thermoplastic resin as raw materials, and that is particularly suitable for producing three-dimensional objects having excellent mechanical properties.
[0039] (The fourth invention) Methods for decomposing used carbon fiber reinforced resin composite materials to obtain recycled carbon fibers include a method in which the resin components are decomposed by heat treatment (thermal decomposition method), a method in which they are dissolved and removed using a solvent, and a method of electrolysis. The method that has been widely used up to now is the method of decomposing by heat treatment.
[0040] When short fiber reinforced thermoplastic resin pellets were produced using conventional recycled carbon fibers obtained by a method of decomposing the fibers through heat treatment, it was difficult to obtain sufficient reinforcing performance.
[0041] The fourth invention of the present disclosure aims to provide recycled carbon fiber reinforced thermoplastic resin pellets that can be used to manufacture molded articles having excellent mechanical strength, using recycled carbon fibers obtained by a method of decomposing the recycled carbon fibers as a raw material. [Means for solving the problem]
[0042] (First aspect of the present invention) The present inventors have found that the above-mentioned problems relating to the first invention can be solved by the following <Aspect A1> to <Aspect A15> according to the first invention. <Aspect A1> Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; 16. A method for decomposing plastic-containing materials, comprising: <Aspect A2> The method of claim A1, wherein the low oxygen concentration gas is introduced into the atmosphere of the furnace while the surface temperature of the plastic-containing material is below 300° C. <Aspect A3> The decomposition method according to aspect A1 or A2, wherein the first surface temperature is from 300°C to 600°C. <Aspect A4> The decomposition method according to any one of A1 to A3, wherein the low oxygen concentration gas is a mixed gas of air and a diluent gas. <Aspect A5> The decomposition method of aspect A4, wherein the diluent gas comprises superheated steam. <Aspect A6> The disassembly method according to any one of A1 to A5, wherein the plastic-containing material and the semiconductor material are arranged at a distance of 50 mm or less from each other. <Aspect A7> The decomposition method according to any one of A1 to A5, wherein the plastic-containing material and the semiconductor material are disposed in contact with each other. <Aspect A8> The decomposition method according to any one of aspects A1 to A7, comprising heating the plastic-containing material that has been subjected to the heat treatment at the first surface temperature in an atmosphere having an oxygen concentration of 10% by volume or more in the presence of a semiconductor material. <Aspect A9> The decomposition method according to any one of aspects A1 to A8, wherein the semiconductor material is an oxide semiconductor material. <Aspect A10> The plastic-containing material contains a plastic and an inorganic material; and The method includes decomposing the plastic in the plastic-containing material by the decomposition method according to any one of aspects A1 to A9, and recovering the inorganic material. Methods for recovering inorganic materials. <Aspect A11> The method of aspect A10, wherein the residual carbon from the plastic recovered with the inorganic material is 5% or less by weight of the inorganic material. <Aspect A12> The method of any one of aspects A10 to A11, wherein the plastic-containing material is a carbon fiber reinforced plastic containing carbon fiber as the inorganic material. <Aspect A13> The method of aspect A12, wherein the recovered carbon fibers have a single fiber tensile strength of 3.0 GPa or greater and a Weibull shape factor of 6.0 or greater. <Aspect A14> Recycled carbon fiber with a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more. <Aspect A15> Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; Including, Here, the plastic-containing material is a carbon fiber reinforced plastic containing carbon fiber. A method for producing recycled carbon fibers having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more.
[0043] (Second Invention) According to the following <Aspect B1> to <Aspect B10> of the second invention of the present disclosure, the above-mentioned problems of the second invention can be solved: <Aspect B1> A blended yarn containing recycled carbon fibers and thermoplastic resin fibers, The recycled carbon fiber has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more; and The recycled carbon fiber contains a residual carbon component, and the content of the residual carbon component is more than 0% by weight and 5.0% by weight or less with respect to the recycled carbon fiber; A blended yarn characterized by: <Mode B2> The blended yarn of aspect B1, wherein the recycled carbon fiber content is greater than 50% and less than or equal to 98% by weight of the blended yarn. <Mode B3> The blended yarn according to aspect B1 or B2, wherein the recycled carbon fibers and the thermoplastic resin fibers each have an average length of 20 mm or more and 80 mm or less. <Aspect B4> The blended yarn according to any one of Aspects B1 to B3, wherein the thermoplastic resin fibers contained in the blended yarn are selected from polyolefin resin fibers, polyester resin fibers, polyamide resin fibers, polyether ketone resin fibers, polycarbonate resin fibers, phenoxy resin fibers, and polyphenylene sulfide resin fibers, and mixtures thereof. <Mode B5> It has a core-sheath structure, The blended yarn according to any one of aspects B1 to B4 is a core component; and The sheath component is a thermoplastic resin; A carbon fiber reinforced thermoplastic resin pellet comprising: <Aspect B6> The carbon fiber reinforced thermoplastic resin pellet according to aspect B5, wherein the thermoplastic resin as the sheath component is selected from polyolefin resins, polyester resins, polyamide resins, polyether ketone resins, polycarbonate resins, phenoxy resins, and polyphenylene sulfide resins, and mixtures thereof. <Aspect B7> The carbon fiber reinforced thermoplastic resin pellet according to aspect B5 or B6, characterized in that the melting point T0 (°C) of the thermoplastic resin as the sheath component is lower than the melting point T1 (°C) of the thermoplastic resin fiber contained in the blended yarn, and T1-T0>10 is satisfied. <Aspect B8> The carbon fiber reinforced thermoplastic resin pellet according to any one of aspects B5 to B7, having a cut length of 3 mm or more and 10 mm or less. <Mode B9> Decomposing plastic components contained in carbon fiber-containing plastic products by semiconductor thermal activation to produce recycled carbon fibers; Blending the recycled carbon fibers with thermoplastic resin fibers; A method for producing a blended yarn, comprising: <Aspect B10> A method for producing carbon fiber-reinforced thermoplastic resin pellets having a core-sheath structure, comprising covering a blended yarn obtained by the method described in aspect B9 with a thermoplastic resin.
[0044] (The Third Invention) According to the following <Aspect C1> to <Aspect C8> of the third invention of the present disclosure, the above-mentioned problems of the third invention can be solved: <Aspect C1> A carbon fiber reinforced thermoplastic resin strand including a blended yarn including recycled carbon fiber and thermoplastic resin fiber, The recycled carbon fiber has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more; and The recycled carbon fiber contains a residual carbon component, and the content of the residual carbon component is more than 0% by weight and 5.0% by weight or less with respect to the recycled carbon fiber; A carbon fiber reinforced thermoplastic resin strand. <Aspect C2> The carbon fiber reinforced thermoplastic resin strand according to aspect C1, wherein the recycled carbon fiber content is greater than 50% by weight and not more than 98% by weight, based on the blended yarn. <Aspect C3> The carbon fiber reinforced thermoplastic resin strand according to aspect C1 or C2, wherein the recycled carbon fibers and the thermoplastic resin fibers each have an average length of 20 mm or more and 80 mm or less. <Aspect C4> The carbon fiber reinforced thermoplastic resin strand according to any one of aspects C1 to C3, wherein the thermoplastic resin fibers are selected from polyolefin resin fibers, polyester resin fibers, polyamide resin fibers, polyether ketone resin fibers, polycarbonate resin fibers, phenoxy resin fibers, and polyphenylene sulfide resin fibers, and mixtures thereof. <Aspect C5> It has a core-sheath structure, The blended yarn is a core component; and The sheath component is a thermoplastic resin; The carbon fiber reinforced thermoplastic resin strand according to any one of aspects C1 to C4, characterized in that: <Aspect C6> A carbon fiber reinforced thermoplastic resin strand according to aspect C5, characterized in that the melting point T0 (°C) of the thermoplastic resin as the sheath component is lower than the melting point T1 (°C) of the thermoplastic resin fiber contained in the blended yarn, and T1-T0>10 is satisfied. <Aspect C7> Decomposing plastic components contained in carbon fiber-containing plastic products by semiconductor thermal activation to produce recycled carbon fibers; The recycled carbon fiber is mixed with a thermoplastic resin fiber to produce a blended yarn. A method for producing the carbon fiber reinforced thermoplastic resin strand according to any one of aspects C1 to C6, comprising: <Aspect C8> A method for producing a three-dimensional object by a fusion deposition method using the carbon fiber reinforced thermoplastic resin strand according to any one of aspects C1 to C6.
[0045] (The fourth invention) According to the following <Aspect D1> to <Aspect D7> of the fourth invention of the present disclosure, the above-mentioned problems of the fourth invention can be solved: <Aspect D1> A carbon fiber reinforced thermoplastic resin pellet containing recycled carbon fiber and a thermoplastic resin, The recycled carbon fiber has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more; and The recycled carbon fiber contains a residual carbon component, and the content of the residual carbon component is more than 0% by weight and 5.0% by weight or less with respect to the recycled carbon fiber; A carbon fiber reinforced thermoplastic resin pellet comprising: <Aspect D2> The carbon fiber reinforced thermoplastic resin pellet according to aspect D1, wherein the recycled carbon fiber content is 5% by weight or more and less than 50% by weight, based on the carbon fiber reinforced thermoplastic resin pellet. <Aspect D3> The carbon fiber reinforced thermoplastic resin pellet according to any one of aspects D1 to D2, wherein the thermoplastic resin is selected from polyolefin resins, polyester resins, polyamide resins, polyetherketone resins, polycarbonate resins, phenoxy resins, and polyphenylene sulfide resins, and mixtures thereof. <Aspect D4> The carbon fiber reinforced thermoplastic resin pellet according to any one of aspects D1 to D3, having a longitudinal length of 3 mm or more and 10 mm or less. <Aspect D5> The carbon fiber reinforced thermoplastic resin pellet according to any one of aspects D1 to D4, wherein the recycled carbon fibers contained in the carbon fiber reinforced thermoplastic resin pellet have an average remaining fiber length of 300 μm or more. <Aspect D6> The carbon fiber reinforced thermoplastic resin pellet according to any one of aspects D1 to D5, which is used to produce a molded article having a tensile strength of 90 MPa or more, a bending strength of 140 MPa or more, and a bending modulus of elasticity of 7100 MPa or more. <Aspect D7> The carbon fiber reinforced thermoplastic resin pellet according to any one of aspects D1 to D6, wherein the frequency of single fibers having a length of 300 μm or less in the recycled carbon fibers in the carbon fiber reinforced thermoplastic resin pellet is 40% or less. Effect of the Invention
[0046] (First aspect of the present invention) According to the first invention of the present disclosure, it is possible to provide a method for decomposing plastic-containing materials, which can stably and efficiently decompose plastic-containing materials.
[0047] Furthermore, according to the first invention of the present disclosure, it is possible to efficiently recover inorganic materials from plastic composite materials containing plastic and inorganic materials.
[0048] (Second Invention) According to the second aspect of the present disclosure, a blended yarn with thermoplastic resin fiber can be provided, which is stably produced using recycled carbon fiber obtained by a method of decomposing the recycled carbon fiber through heat treatment as a raw material. Also, according to the second aspect of the present disclosure, a carbon fiber reinforced thermoplastic resin pellet formed from the blended yarn can be provided.
[0049] (The Third Invention) According to the third invention of the present disclosure, it is possible to provide a carbon fiber-reinforced thermoplastic resin strand that can be stably produced using recycled carbon fiber obtained by a method of decomposing through heat treatment and thermoplastic resin fiber as raw materials, and that is particularly suitable for producing three-dimensional objects having excellent mechanical properties.
[0050] (The fourth invention) According to the fourth invention of the present disclosure, it is possible to provide recycled carbon fiber reinforced thermoplastic resin pellets that can be used to manufacture molded articles having excellent mechanical properties, using recycled carbon fibers obtained by a method of decomposing through heat treatment as a raw material.
[0051] In particular, according to the carbon fiber reinforced thermoplastic resin pellets according to the fourth invention of the present disclosure, it is possible to produce molded articles having mechanical strength equivalent to that of molded articles produced from carbon fiber reinforced thermoplastic resin pellets produced using virgin carbon fiber (normal carbon fiber that is not recycled carbon fiber) as the raw material. [Brief description of the drawings]
[0052] [Figure 1] FIG. 1 is a conceptual cross-sectional view for explaining a disassembly method according to the first invention of the present disclosure. [Diagram 2] FIG. 2 is a schematic cross-sectional view showing one embodiment of the disassembly method according to the first invention of the present disclosure. [Diagram 3] Figure 3 is a photograph of the CFRP plate before heat treatment. [Figure 4] FIG. 4 is a photograph of the CFRP plate after undergoing the treatment according to Examples 1-4. [Diagram 5]FIG. 5 is a photograph of the CFRP plate after the treatment according to Comparative Example 1-2. [Figure 6] FIG. 6 is a schematic diagram of a carbon fiber reinforced thermoplastic resin pellet according to the second invention of the present disclosure and a carbon fiber reinforced thermoplastic resin strand used in the process of producing the pellet according to the second invention of the present disclosure. [Figure 7] FIG. 7 is a schematic diagram of a carbon fiber reinforced thermoplastic resin strand according to the third invention of the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0053] (First aspect of the present invention) <How to disassemble plastic-containing materials> The method for decomposing plastic-containing materials according to the first aspect of the present disclosure comprises: Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; Includes.
[0054] 1 is a conceptual cross-sectional view for explaining the decomposition method according to the first aspect of the present invention. The decomposition mechanism of the plastic-containing material according to the first aspect of the present invention will be described below. Note that there is no intention to limit the present invention by theory.
[0055] When the semiconductor material 11 is heated in an oxygen atmosphere, holes h + and e - This electron e - is the oxygen in the atmosphere, O 2 Reacts with O 2 - It is believed that radicals (active oxygen) are generated. Then, radical propagation occurs in the plastic-containing material 12 disposed adjacent to the semiconductor material 11, and the plastic-containing material 12 is decomposed into low molecular weight components, and further CO 2 , H 2 O, C.H. 4It is believed that the radicals promote the oxidative decomposition of plastics by abstracting hydrogen from the plastics.
[0056] By using a semiconductor material, it is possible to reduce the heat introduced for decomposing plastics, as compared to a case in which a semiconductor material is not used, and as a result, it is possible to reduce the amount of energy consumption.
[0057] Conventional plastic decomposition methods based on the thermal activation of semiconductors can sometimes generate excessive heat due to oxidation during the heat treatment process. In conventional methods, heat treatment is carried out in an atmosphere where the oxygen concentration is not controlled, which generates excessive radicals, which is thought to result in excessive heat generation due to oxidation.
[0058] In response to this, the present inventors have discovered that even in the presence of semiconductor materials, by setting the oxygen concentration to a relatively low value, it is possible to efficiently heat-treat plastics while suppressing excessive heat generation due to oxidation.
[0059] In particular, in the early stages of the thermal decomposition of plastics, there is a high possibility that excessive heat generation due to oxidation will occur due to the relatively large amount of plastic. In contrast, according to the method according to the first aspect of the present disclosure, the heat treatment is efficiently performed at a relatively low oxygen concentration, so that the generation of excessive heat generation due to oxidation can be suppressed even in the early stages of decomposition.
[0060] Therefore, according to the method of the first aspect of the present disclosure, since the heat treatment is performed in the presence of a semiconductor material, good decomposition efficiency can be obtained even at a relatively low oxygen concentration, and by setting the oxygen concentration in the heating furnace to a relatively low value, it is possible to suppress excessive oxidation heat generation and achieve a decomposition treatment with improved stability.
[0061] The disassembly method according to the first aspect of the present disclosure will be described with reference to the drawings depicting an exemplary embodiment.
[0062] Fig. 2 is a cross-sectional view showing a schematic diagram of one embodiment of the decomposition method according to the first invention of the present disclosure. The heating furnace 20 shown in Fig. 2 has a heat source (heater) 23, a gas supply unit 24, an exhaust port 25, and an internal space 26. A porous carrier 21 is disposed in the internal space 26 of the heating furnace 20, and a semiconductor material is supported on the surface of the carrier 21. In the embodiment of Fig. 2, a plastic-containing material 22 is disposed in contact with the carrier 21.
[0063] The temperature of the atmosphere in the interior space 26 of the furnace 20 can be controlled via the heat source (heater) 23 of the furnace 20, so that the surface temperature of the plastic-containing material 22 is at a specific temperature. The surface temperature of the plastic-containing material 22 can be measured via a temperature sensor 27 located within 5 mm from the surface of the plastic-containing material 22.
[0064] A low oxygen concentration gas having an oxygen concentration of less than 10% by volume is introduced into the internal space 26 of the furnace 20 through a gas supply unit 24. The oxygen concentration of the atmosphere in the furnace 20 can be controlled by setting the introduction speed of the low oxygen concentration gas according to the furnace volume. The low oxygen concentration gas can be forced into the furnace through a gas supply unit provided in the furnace, for example, or can be sucked into the furnace by applying suction pressure to the exhaust port 25.
[0065] The low-oxygen gas is, for example, a mixed gas of air and nitrogen gas. The oxygen concentration in the heating furnace can be controlled by selecting the ratio of air to nitrogen gas.
[0066] In an atmosphere in which the oxygen concentration is controlled to less than 10% by volume by introducing a low-oxygen concentration gas, the plastic-containing material is heated to a first surface temperature, for example, a first surface temperature of 300° C. to 600° C. As a result, the plastic contained in the plastic-containing material 22 is decomposed into decomposition gases such as water vapor, carbon dioxide, and methane, and the decomposition gases are exhausted from the exhaust port 25 of the heating furnace 20.
[0067] After the above-mentioned heat treatment at an oxygen concentration of less than 10% by volume, a further heat treatment can be carried out in which the oxygen concentration is increased to 10% by volume or more.
[0068] Furthermore, after the heat treatment, the inorganic materials contained in the plastic-containing material can be recovered.
[0069] The disassembly method according to the first aspect of the present disclosure will be described in more detail below.
[0070] <Materials containing plastic> A plastic-containing material contains plastic. A plastic-containing material may be a plastic material or a plastic composite material.
[0071] The plastics contained in the plastic-containing material include thermoplastic resins and thermosetting resins.
[0072] Examples of thermoplastic resins contained in the plastic-containing material include polycarbonate (PC) resin, polyethylene (PE) resin, polypropylene (PP) resin, polyvinyl chloride (PVC) resin, polystyrene (PS) resin, polyethylene terephthalate (PET) resin, acrylonitrile-butadiene-styrene (ABS) resin, polyamide (PA) resin, polylactic acid (PLA) resin, polyimide (PI) resin, polymethyl methacrylate (PMMA) resin, methacrylic resin, polyvinyl alcohol (PVA) resin, polyacetal resin, petroleum resin, AS resin, modified polyphenylene ether resin, polybutylene terephthalate (PBT) resin, polybutene (PB) resin, fluororesin, polyacrylate resin, polyether ether ketone (PEEK) resin, and polyphenylene sulfide (PPS) resin.
[0073] Examples of the thermosetting resin contained in the plastic-containing material include phenol resin, urethane foam resin, polyurethane resin, urea resin, epoxy resin, unsaturated polyester resin, melamine resin, alkyd resin, vinyl ester resin, and cyanate resin.
[0074] The plastic-containing material may contain at least one resin selected from the group consisting of the thermoplastic resins and thermosetting resins described above.
[0075] (Plastic Composites) The plastic-containing material is particularly a plastic composite material. The plastic composite material is, for example, a fiber reinforced plastic (FRP). Examples of reinforcing fibers contained in the fiber reinforced plastic include glass fiber, aramid fiber, and carbon fiber.
[0076] (Carbon Fiber Reinforced Plastics) The plastic composite material is particularly a plastic product containing carbon fiber, such as carbon fiber reinforced plastic (CFRP). Carbon fiber reinforced plastic contains plastic and carbon fiber (carbon fiber material). Carbon fiber reinforced plastic may contain other members and / or materials (for example, reinforcing fibers other than carbon fiber, resin moldings, metals, ceramics, etc.).
[0077] The carbon fiber is not particularly limited, but may be a PAN-based carbon fiber or a pitch-based carbon fiber. The carbon fiber may be one type or may be composed of two or more types.
[0078] The carbon fibers contained in the carbon fiber reinforced plastic may be in any form, for example, a carbon fiber bundle, a fabric formed from carbon fiber bundles, or a nonwoven fabric of carbon fibers.
[0079] <Introduction of low oxygen concentration gas> In the method according to the first aspect of the present disclosure, A low-oxygen concentration gas having an oxygen concentration of less than 10% by volume is introduced into the atmosphere of the heating furnace.
[0080] Preferably, the oxygen concentration of the low-oxygen concentration gas introduced into the atmosphere of the heating furnace is greater than 0 vol.%, 1 vol.% or more, 2 vol.% or more, 3 vol.% or more, or 4 vol.% or more, and / or 9 vol.% or less, 8 vol.% or less, or 7 vol.% or less.
[0081] The timing of introducing the low-oxygen concentration gas into the heating furnace can be determined according to the type of plastic contained in the plastic-containing material, the surface temperature at which the plastic starts to decompose, etc. In addition, the timing of introducing the low-oxygen concentration gas into the heating furnace can be determined based on data previously obtained regarding the self-heating of the plastic-containing material.
[0082] In one preferred embodiment of the first invention of the present disclosure, a low oxygen concentration gas is introduced into the atmosphere of the furnace while the surface temperature of the plastic-containing material held in the furnace is less than 300°C.
[0083] More preferably, a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume is introduced into the atmosphere of the heating furnace while the surface temperature of the plastic-containing material held in the heating furnace is 250° C. or less, 200° C. or less, or 150° C. or less. The lower limit of the surface temperature of the plastic-containing material held in the heating furnace when introducing a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume into the atmosphere of the heating furnace is not particularly limited, and may be, for example, 0° C. or more, 10° C. or more, 20° C. or more, or room temperature or more.
[0084] More preferably, a low-oxygen gas having an oxygen concentration of less than 10% by volume is introduced into the atmosphere of a furnace, particularly a furnace holding a plastic-containing material having a surface temperature of less than 300°C, thereby making the oxygen concentration of the atmosphere in the furnace less than 10% by volume.
[0085] More preferably, a low-oxygen gas having an oxygen concentration of less than 10% by volume is introduced into the atmosphere of a furnace, in particular a furnace holding a plastic-containing material having a surface temperature of less than 300°C, thereby controlling the oxygen concentration in the atmosphere in the furnace to greater than 0% by volume, 1% or more by volume, 2% or more by volume, 3% or more by volume, or 4% or more by volume, and / or 9% or less by volume, 8% or less, or 7% or less by volume.
[0086] The oxygen concentration in the furnace can be measured directly by an oxygen concentration meter (oxygen monitor) or can be determined based on the furnace volume and the amount of gas introduced into the furnace. The oxygen concentration in the furnace is preferably the average oxygen concentration over the course of the heat treatment.
[0087] The low oxygen concentration gas can be introduced into the furnace, for example, by forcing the low oxygen concentration gas into the furnace through a gas supply unit provided in the furnace, or by suctioning through an inlet (or exhaust) provided in the furnace, thereby allowing gas to flow into the furnace from a gas supply unit provided at a location different from the inlet. The gas supply unit of the furnace may, for example, have an opening and / or may have a gas-permeable material.
[0088] The amount of gas introduced into the furnace can be set based on the unit resin amount of the resin (eg, epoxy resin) to be decomposed, depending on the capacity of the heating furnace, the desired oxygen concentration, and the like.
[0089] For example, the amount of gas introduced into the furnace per unit amount of resin can be determined within a range of 1 to 1000 (L / min) / kg or less, preferably within a range of 2 to 700 (L / min) / kg or less. In addition, the time for replacing the atmosphere in the furnace with the introduced gas can be determined based on the determined amount of gas introduced and the volume of the heating furnace used.
[0090] In particular, the amount of low-oxygen gas introduced relative to the furnace volume can be set so that the atmosphere in the furnace is replaced by the introduced low-oxygen gas while the surface temperature of the plastic-containing material held in the furnace is below 300°C.
[0091] The low-oxygen gas introduced into the heating furnace may contain a diluent gas, and is particularly a mixed gas of air and a diluent gas. Examples of the diluent gas include nitrogen gas, carbon dioxide gas, steam, and superheated steam. Note that superheated steam is steam heated to a temperature equal to or higher than the boiling point. Superheated steam has the advantage of having a relatively high heat transfer rate to the object to be decomposed.
[0092] (heating furnace) The heating furnace may be a combustion furnace or an electric furnace. The heating furnace may have, for example, an internal space for accommodating the plastic-containing material and the semiconductor material, a heat source (heater) for heating the atmosphere in the heating furnace, a gas supply unit for introducing a low-oxygen concentration gas into the heating furnace, an exhaust port for discharging the decomposition gas, and, optionally, a suction port for applying suction pressure to the inside of the heating furnace. Note that one structure may be used as the exhaust port and the suction port. For example, one or more openings provided in the heating furnace may be used as the exhaust port and / or the suction port.
[0093] (Surface temperature) The "skin temperature" of a plastic-containing material can be determined by measuring the temperature within 5 mm around the plastic-containing material during the heat treatment.
[0094] The surface temperature of the plastic-containing material can be controlled, for example, by controlling the temperature in the furnace via the heat source of the furnace and / or by introducing a cold gas into the furnace and / or by reducing the oxygen concentration to suppress oxidation heat generation.
[0095] In addition, the surface temperature of the plastic-containing material can be measured using a temperature sensor placed within 5 mm from the surface of the plastic-containing material and this measurement value can be fed back to the heat source of the heating furnace, thereby controlling the surface temperature with even greater precision.
[0096] Furthermore, for example, data regarding the correlation between the temperature inside the heating furnace and / or the output of the heat source and the surface temperature measured by a sensor may be obtained in advance, and the heat treatment may be performed based on this data.
[0097] <Heat treatment> The method according to the first aspect of the present disclosure comprises: Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; Includes.
[0098] Preferably, this heat treatment is carried out in an atmosphere in which the oxygen concentration is less than 10 vol.% by introducing a low-oxygen concentration gas having an oxygen concentration of less than 10 vol.%, and in particular, is carried out under an oxygen concentration of more than 0 vol.%, 1 vol.% or more, 2 vol.% or more, 3 vol.% or more, or 4 vol.% or more, and / or is carried out under an oxygen concentration of 9 vol.% or less, 8 vol.% or less, or 7 vol.% or less.
[0099] (1st surface temperature) The "first surface temperature" is the surface temperature of the plastic-containing material. The "first surface temperature" can be determined by measuring the temperature within 5 mm around the plastic-containing material during the heat treatment, similar to the "surface temperature" described above.
[0100] The first surface temperature may be 300° C. or more, 325° C. or more, or 350° C. or more, and / or 600° C. or less, 550° C. or less, 500° C. or less, or 450° C. or less. The first surface temperature is, for example, 300° C. to 600° C., 300° C. to 550° C., 300° C. to 500° C., or 300° C. to 450° C.
[0101] If the first surface temperature is below the above range, decomposition of the plastic may not occur. If the first surface temperature exceeds the above range, when the plastic-containing material contains valuables such as carbon fibers, deterioration and / or burning of the valuables such as carbon fibers due to heating in the presence of oxygen may become significant. By setting the first surface temperature at a relatively low temperature, the effect of suppressing excessive oxidation heat generation is further enhanced.
[0102] In a preferred embodiment of the first invention of the present disclosure, the first surface temperature is set to 450° C. or higher during the heat treatment at an oxygen concentration of less than 10% by volume. When the heating temperature is relatively low, further decomposition of the plastic may be inhibited by char generated on the surface of the plastic-containing material, but by setting the surface temperature to 450° C. or higher, the char can be removed even at a relatively low oxygen concentration. This makes it possible to further improve the decomposition efficiency of the plastic.
[0103] Preferably, the heat treatment is carried out for a predetermined time under introduction of a low oxygen concentration gas with an oxygen concentration of less than 10% by volume. This predetermined time may be 1 to 600 minutes, preferably 30 to 300 minutes, and more preferably 60 to 180 minutes. The start point of the "predetermined time" may be the time when the temperature of the heating furnace reaches 300°C or the time when the start of decomposition of the plastic is confirmed.
[0104] (Semiconductor materials) The semiconductor material may be placed in the furnace along with the plastic-containing material, or the semiconductor material may be placed in the furnace first and then the plastic-containing material may be placed adjacent to or in contact with the semiconductor material.
[0105] In one embodiment according to the first invention of the present disclosure, the plastic-containing material and the semiconductor material to be subjected to the heat treatment are arranged at a distance of 50 mm or less from each other. For this purpose, for example, a spacer arranged between the plastic-containing material and the semiconductor material can be used. In this case, the lower limit of the distance is not particularly limited, but may be more than 0 mm, more than 1 mm, more than 5 mm, or more than 10 mm.
[0106] The distance between the plastic-containing material and the semiconductor material can be measured where they are closest to each other.
[0107] In another preferred embodiment according to the first aspect of the present disclosure, the plastic-containing material to be subjected to the heat treatment and the semiconductor material are placed in contact with each other.
[0108] The manner of contact between the plastic-containing material and the semiconductor material is not particularly limited. For example, the two can be contacted by placing the plastic-containing material on the semiconductor material. The plastic-containing material may also be placed on the semiconductor material supported on the surface of the carrier. Furthermore, the two can be contacted by surrounding or covering at least a part or the whole of the plastic-containing material with the semiconductor material.
[0109] The semiconductor material is not particularly limited as long as it is stable at the temperature and oxygen concentration of the present invention. The semiconductor material contains, for example, at least one selected from the group consisting of the following substances: BeO, MgO, CaO, SrO, BaO, CeO 2 ,ThO 2 ,UO 3 ,U 3 O 8 ,TiO 2 ,ZrO 2 ,V 2 O 5 ,Y 2 O 3 ,Y 2 O 2 S,Nb 2 O 5 ,Ta 2O 5 ,MoO 3 , WO 3 ,MnO 2 ,Fe 2 O 3 ,MgFe 2 O 4 ,NiFe 2 O 4 ,ZnFe 2 O 4 ,ZnCo 2 O 4 ,ZnO,CdO,Al 2 O 3 ,MgAl 2 O 4 ,ZnAl 2 O 4 , 2 O 3 , In 2 O 3 , SiO 2 , SnO 2 ,PbO 2 ,UO 2 , Cr 2 O 3 ,MgCr 2 O 4 ,FeCrO 4 ,CoCrO 4 ,ZnCr 2 O 4 , WO 2 ,MnO,Mn 3 O 4 Mr 2 O 3 ,FeO,NiO,CoO,Co 3 O 4 ,PdO,CuO,Cu 2 Oh, Ag 2 Oh, CoAl 2 O 4 ,NiAl 2 O 4 , 2 O,GeO,PbO,TiO,Ti 2 O 3 ,VO,MoO 2 ,IrO 2 ,RuO 2 ,CdS、CdSe、CdTe、Cu 2 O、Sb 2 O 3 、MnO 3, and CoCrO 4 .
[0110] Preferably, the semiconductor material is an oxide semiconductor material, such as chromium oxide, titanium oxide, zinc oxide, vanadium oxide, tungsten oxide, molybdenum oxide, cobalt oxide, iron oxide, and copper oxide.
[0111] The shape of the semiconductor material is not particularly limited, and may be, for example, a plate-like, granular, or honeycomb shape. From the viewpoint of promoting the decomposition of plastics, it is preferable that the semiconductor material is supported on the surface of an air-permeable carrier. The air-permeable carrier may be a porous body made of ceramics or the like, a honeycomb-shaped support, or the like. The semiconductor material may be a sintered body of a semiconductor.
[0112] <Two-stage heating> A heat treatment method according to one preferred embodiment of the first invention according to the present disclosure includes: Heating the plastic-containing material subjected to the heat treatment at the first surface temperature in an atmosphere having an oxygen concentration of 10% by volume or more in the presence of a semiconductor material; Includes.
[0113] Heat treatment at an oxygen concentration of 10 vol.% or more is preferably carried out under an oxygen concentration of more than 10 vol.%, 12 vol.% or more, 15 vol.% or more, or 20 vol.% or more, and / or at an oxygen concentration of 30 vol.% or less, or 25 vol.% or less.
[0114] In this embodiment, also referred to as two-stage heating, the plastic-containing material that has been heat treated at a relatively low oxygen concentration is subjected to a further heat treatment under an increased oxygen concentration.
[0115] In the initial stage of the thermal decomposition of plastics, there is a high possibility that excessive heat generation due to oxidation will occur due to the relatively large amount of plastic. In contrast, in the above embodiment involving two-stage heating, a heat treatment with a relatively low oxygen concentration is performed, followed by a heat treatment with an increased oxygen concentration. In other words, heating with an increased oxygen concentration is performed at a stage when the decomposition of plastics has progressed and the amount of plastic has decreased, so that the generation of excessive heat generation due to oxidation can be suppressed.
[0116] In addition, in heat treatment at a relatively low oxygen concentration, some of the plastic may not vaporize and remain as char. In contrast, in the above embodiment involving two-stage heating, the oxygen concentration is increased and further heat treatment is performed, so that the remaining char can be efficiently decomposed and removed, and as a result, the decomposition efficiency can be further improved.
[0117] Heat treatment under the introduction of a low oxygen concentration gas with an oxygen concentration of less than 10% by volume and heat treatment at an oxygen concentration of 10% by volume or more can be performed consecutively in the same heating furnace. That is, for example, after the plastic-containing material is heated to a first surface temperature, the oxygen concentration can be increased to 10% by volume or more in the same heating furnace, and further heat treatment can be performed. In conventional plastic decomposition methods, it was necessary to perform processing such as shredding of the processing target following batch processing, but by performing heat treatment under the introduction of a low oxygen concentration gas with an oxygen concentration of less than 10% by volume and heat treatment at an oxygen concentration of 10% by volume or more consecutively in the same heating furnace, it is possible to reduce the number of steps.
[0118] The atmosphere with an oxygen concentration of 10% by volume or more can be formed, for example, by introducing an oxygen-rich gas having an oxygen concentration of 10% by volume or more into the heating furnace, particularly by introducing air and / or oxygen gas into the heating furnace. The oxygen concentration of the oxygen-rich gas may be more than 10% by volume, 12% by volume or more, 15% by volume or more, or 20% by volume or more, and / or 30% by volume or less, or 25% by volume or less.
[0119] In the heat treatment at an oxygen concentration of 10 volume % or more, the semiconductor material used in the heat treatment at the first surface temperature can be used.
[0120] (2nd surface temperature) In particular, the plastic-containing material that has been subjected to a heat treatment at a first surface temperature is heated to a second surface temperature in the presence of a semiconductor material and in an atmosphere with an oxygen concentration of 10% by volume or more.
[0121] The "second surface temperature" is the surface temperature of the plastic-containing material to be treated. The "second surface temperature" can be determined by measuring the temperature within 5 mm around the plastic-containing material during the heat treatment, similar to the above-mentioned "surface temperature" and "first surface temperature".
[0122] The second surface temperature may be in the range of 400°C to 600°C. More preferably, the second surface temperature is in the range of 425°C to 575°C, or 450°C to 550°C.
[0123] If the second surface temperature is below the above range, the decomposition efficiency may not be improved. If the second surface temperature exceeds the above range, when the plastic-containing material contains valuables such as carbon fibers, the valuables such as carbon fibers may be significantly deteriorated and / or burned due to heating in the presence of oxygen.
[0124] The second surface temperature may be substantially the same temperature as the first surface temperature.
[0125] The second surface temperature may be equal to or higher than the first surface temperature, or may be at least 5° C., at least 10° C., at least 25° C., at least 50° C., or at least 75° C. higher than the first surface temperature. The upper limit of the difference between the first surface temperature and the second surface temperature is not particularly limited, and may be, for example, 200° C. or less, or 100° C. or less.
[0126] The heat treatment at an oxygen concentration of 10% by volume or more can be carried out for a predetermined time, which may be, for example, 1 to 600 minutes, 60 to 360 minutes, or 90 to 300 minutes.
[0127] <Application> According to the method for decomposing plastic-containing materials according to the first aspect of the present disclosure, a wide variety of plastics can be efficiently vaporized and decomposed. The decomposition method according to the first aspect of the present disclosure can also be applied to volatile organic compounds (VOCs), exhaust gas, particulate matter (PM), etc., and can also be used for exhaust gas treatment.
[0128] <Method for recovering inorganic or metallic materials> <Recovery method for inorganic materials> The first invention of the present disclosure also relates to a method for recovering inorganic materials contained in a plastic composite material.
[0129] In one embodiment of the recovery method according to the first invention of the present disclosure, the plastic-containing material, which is a plastic composite material, contains plastic and an inorganic material, and the recovery method includes: Decomposing plastics in a plastic-containing material by the decomposition method according to the first aspect of the present disclosure to recover inorganic materials; Includes. For the decomposition method that can be used in the recovery method according to the first invention of the present disclosure and its details, reference can be made to the above description of the decomposition method for plastic-containing materials.
[0130] As described above, the decomposition method according to the first aspect of the present disclosure can efficiently decompose plastics. Therefore, the recovery method according to the first aspect of the present disclosure can efficiently and selectively decompose plastics contained in a plastic composite material, and therefore can efficiently recover inorganic materials with good physical properties.
[0131] In addition, in the recovery method according to the first aspect of the present disclosure, inorganic materials can be recovered without crushing the plastic composite material. Crushing the plastic composite material is not particularly excluded, and crushing can be performed at will.
[0132] Furthermore, when recovering inorganic materials from plastic composite materials, it is necessary to suppress the influence of heat treatment on the inorganic materials as much as possible in order to maintain the quality of the recovered inorganic materials. In this regard, in the decomposition method according to the first invention of the present disclosure, excessive oxidation heat generation is suppressed by a relatively low oxygen concentration. Therefore, according to the recovery method according to the first invention of the present disclosure, it is possible to recover inorganic materials with relatively good physical properties.
[0133] (Two-stage heating) In another embodiment of the recovery method according to the first aspect of the present disclosure, the plastic-containing material as a plastic composite material is subjected to two-stage heating, that is, the plastic composite material is subjected to heating under the introduction of a low-oxygen concentration gas (oxygen concentration less than 10%) and then a heat treatment with an oxygen concentration of 10% by volume or more, thereby decomposing the plastic and recovering the inorganic material.
[0134] When recovering inorganic materials, it is desirable to suppress deterioration of the inorganic material's physical properties due to excessive oxidation heat generation, and furthermore, it is preferable to suppress deterioration of the inorganic material's physical properties due to carbonization of plastics and remaining attached to the inorganic material. In this regard, in the embodiment in which the plastic composite material is subjected to two-stage heating, the oxygen concentration is made relatively low in the initial stage where excessive oxidation heat generation is likely to occur, thereby suppressing deterioration of the inorganic material's physical properties due to excessive oxidation heat generation. Furthermore, since a heat treatment with an increased oxygen concentration is performed after that, the carbonized resin remaining on the inorganic material can be efficiently removed. As a result, the method for recovering inorganic materials via a two-stage heating treatment can ensure even better physical properties of the recovered inorganic material.
[0135] (Inorganic materials) Plastic composite materials containing inorganic materials and plastics include fiber reinforced plastics (FRP), particularly carbon fiber reinforced plastics.
[0136] The inorganic materials include inorganic fibers, such as alumina fibers, ceramic fibers, silica fibers, etc. The inorganic fibers are in particular carbon fibers (carbon fiber materials).
[0137] (Carbon Fiber) The carbon fiber is not particularly limited, but may be a PAN-based carbon fiber or a pitch-based carbon fiber. The carbon fiber may be one type or may be composed of two or more types.
[0138] The carbon fibers may be in any form, for example, carbon fiber bundles, a fabric formed from carbon fiber bundles, or a nonwoven carbon fiber fabric.
[0139] (Collected items) According to one embodiment of the recovery method according to the first invention of the present disclosure, the residual carbon derived from plastics recovered together with the inorganic material is reduced, and in particular, the residual carbon is 5% by weight or less of the inorganic material recovered. Preferably, the residual carbon is 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.9% by weight or less, 0.5% by weight or less, or 0.1% by weight or less of the inorganic material recovered. It is preferable that the residual carbon is reduced as much as possible, but the lower limit may be 0.001% by weight or more. The amount of residual carbon in the recovered inorganic material can be measured in the same manner as the amount of residual carbon in recycled carbon fiber described later.
[0140] Furthermore, according to the recovery method according to the first aspect of the present disclosure, it is possible to recover carbon fibers having better physical properties than the carbon fibers before the carbon fiber reinforced plastic is produced.
[0141] In particular, according to the recovery method according to the first aspect of the present disclosure, carbon fibers having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more can be obtained as an inorganic material from carbon fiber reinforced plastic.
[0142] (single fiber tensile strength) The single fiber tensile strength is preferably 3.1 GPa or more, 3.2 GPa or more, 3.3 GPa or more, or 3.4 GPa or more. The upper limit of the single fiber tensile strength is not particularly limited, but may be 6.0 GPa or less.
[0143] The single fiber tensile strength can be measured according to JIS R7606 as follows: At least 30 single fibers are taken from the fiber bundle. The diameter of the single fiber is measured in a side image of the single fiber taken by a digital microscope, and the cross-sectional area is calculated. The sampled single fiber was fixed to a perforated mount using adhesive. The mount on which the single fiber was fixed was attached to a tensile tester, and a tensile test was performed with a test length of 10 mm and a strain rate of 1 mm / min to measure the tensile breaking stress. The tensile strength is calculated from the cross-sectional area and tensile breaking stress of the single fiber. The single fiber tensile strength is the average of the tensile strengths of at least 30 single fibers.
[0144] (Weibull shape factor) The Weibull shape coefficient is preferably 6.5 or more, 7.0 or more, 7.5 or more, 8.0 or more, or 8.5 or more. The upper limit of the Weibull shape coefficient is not particularly limited, but may be 15.0 or less. A high Weibull shape coefficient of single fiber tensile strength means that the variation in single fiber tensile strength is small.
[0145] The Weibull shape factor can be calculated according to the following formula: lnln{1 / (1-F)}=m×lnσ+C In the formula, F is the fracture probability obtained by the symmetric sample cumulative distribution method, σ is the single fiber tensile strength (MPa), m is the Weibull shape coefficient, and C is a constant.
[0146] The Weibull shape factor m can be obtained by plotting lnln{1 / (1-F)} against lnσ and calculating the linear approximation slope.
[0147] <Method of recovering metal materials> In another embodiment of the recovery method according to the first invention of the present disclosure, metal materials are recovered from a plastic-containing material that contains plastic and metal materials.
[0148] That is, according to one embodiment of the method according to the first aspect of the present disclosure, there is provided a method for recovering metal materials, comprising: The plastic-containing material contains a plastic and a metal material, and Decomposing plastics in plastic-containing materials using the decomposition method according to the first aspect of the present disclosure, and recovering metal materials.
[0149] Examples of metal materials include gold and rare metals.
[0150] Plastic composite materials containing metal materials and plastics include, for example, composite materials having metal materials encapsulated in a matrix resin, particularly solar panels, electronic components, and electronic circuits.
[0151] <Application> According to the recovery method of the first invention of the present disclosure, for example, only the matrix resin of fiber reinforced plastics (FRP), solar panels, electronic circuits, etc. can be efficiently decomposed, and valuable materials such as reinforcing fibers and rare metals can be efficiently recovered.
[0152] <Recycled carbon fiber (recycled carbon fiber material)> The recycled carbon fiber (recycled carbon fiber material) according to the first invention of the present disclosure can be produced by recovering carbon fibers from carbon fiber reinforced plastic. In one embodiment of the first invention of the present disclosure, the recycled carbon fiber can have better physical properties than the carbon fiber before the carbon fiber reinforced plastic is produced.
[0153] The method for producing the recycled carbon fiber is not particularly limited. For example, the recycled carbon fiber can be produced by recovering the recycled carbon fiber from the carbon fiber reinforced plastic by the recovery method according to the first invention of the present disclosure.
[0154] In one embodiment, the recycled carbon fibers have a single fiber tensile strength of 3.0 GPa or more and a Weibull shape factor of 6.0 or more. The single fiber tensile strength and Weibull shape factor can be measured and determined by the methods described above.
[0155] The single fiber tensile strength of the recycled carbon fibers is preferably 3.1 GPa or more, 3.2 GPa or more, 3.3 GPa or more, or 3.4 GPa or more. The upper limit of the single fiber tensile strength is not particularly limited, but may be 6.0 GPa or less.
[0156] The Weibull shape coefficient of the recycled carbon fibers is preferably 6.5 or more, 7.0 or more, 7.5 or more, 8.0 or more, or 8.5 or more. The upper limit of the Weibull shape coefficient is not particularly limited, but may be 15.0 or less.
[0157] (Method of manufacturing recycled carbon fiber (recycled carbon fiber material)) In particular, a method for producing recycled carbon fibers having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape factor of 6.0 or more, comprising: Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; Including, Here, the plastic-containing material is a carbon fiber reinforced plastic containing carbon fibers.
[0158] In particular, a method for producing recycled carbon fibers having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more is provided, A method for decomposing plastics in a plastic-containing material by heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, and then heating the plastic-containing material that has been subjected to heat treatment at the first surface temperature in an atmosphere having an oxygen concentration of 10% by volume or more, in the presence of a semiconductor material; Including, Here, the plastic-containing material is a carbon fiber reinforced plastic containing carbon fibers.
[0159] In one preferred embodiment of the method for producing recycled carbon fiber according to the first invention of the present disclosure, a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume is introduced into the atmosphere of a heating furnace while the surface temperature of the plastic-containing material is less than 300°C.
[0160] (carbon residue) Preferably, in the recycled carbon fiber according to the first invention of the present disclosure, the amount of residual carbon (residual carbon component) is reduced, and in particular, the residual carbon is 5% by weight or less relative to the recycled carbon fiber. More preferably, the residual carbon is 4% by weight or less, 3% by weight or less, 2% by weight or less, 1% by weight or less, 0.9% by weight or less, 0.5% by weight or less, or 0.1% by weight or less relative to the recycled carbon fiber. It is preferable that the amount of residual carbon is reduced as much as possible, and the lower limit is not particularly limited, but it may be, for example, 0.01% by weight or more relative to the recycled carbon fiber.
[0161] It should be noted that "residual carbon" is a carbonized component derived from the plastic contained in the carbon fiber reinforced plastic, which is the raw material used in producing recycled carbon fiber.
[0162] The amount of residual carbon (residual carbon component) in the recycled carbon fiber can be determined by thermogravimetric analysis (TGA).
[0163] The determination of the carbon residue by thermogravimetry can be carried out by the following procedure: (i) A sample piece of 1 to 4 mg obtained by crushing the recycled carbon fiber was subjected to a thermogravimetric analysis at an air supply rate of 0.2 L / min, a heating rate of 5°C / min, and a recording speed of 1 / 6 s. Heating from room temperature to 100°C, Hold at 100°C for 30 minutes, Heating from 100°C to 400°C, and Hold at 400℃ The thermogravimetric analysis was carried out for a total of 300 minutes. (ii) In a graph in which the weight loss rate is plotted against time, an inflection point in the slope is identified, and the amount of residual carbon is calculated by subtracting the weight loss rate during the holding period at 100°C from the weight loss rate value at that inflection point.
[0164] If an inflection point of the slope cannot be identified under the above conditions, instead of a total of 300 minutes of thermogravimetric analysis, a total of about 600 minutes of thermogravimetric analysis may be performed with a hold at 400°C for 480 minutes, and further, instead of holding at 400°C for 480 minutes, a specific temperature in the range of more than 400°C to 500°C may be held for 480 minutes. In addition, when the recycled carbon fibers contain resin derived from a sizing agent or the like, the above measurement can be performed after removing the resin.
[0165] In particular, a method for producing recycled carbon fibers having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more, and a residual carbon content of more than 0% by weight and 5.0% by weight or less based on the recycled carbon fibers, comprising: Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; Including, Here, the plastic-containing material is a carbon fiber reinforced plastic containing carbon fibers.
[0166] In particular, a method for producing recycled carbon fibers having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more, and a residual carbon content of more than 0% by weight and not more than 5.0% by weight based on the recycled carbon fibers, comprising the steps of: A method for decomposing plastics in a plastic-containing material by heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of less than 10% by volume has been introduced, in the presence of a semiconductor material, and then heating the plastic-containing material that has been subjected to heat treatment at the first surface temperature in an atmosphere having an oxygen concentration of 10% by volume or more, in the presence of a semiconductor material; Including, Here, the plastic-containing material is a carbon fiber reinforced plastic containing carbon fibers.
[0167] (Second Invention) The second invention of the present disclosure relates to a blended yarn of recycled carbon fiber and thermoplastic resin fiber, and a carbon fiber reinforced thermoplastic resin pellet formed from the blended yarn. The second invention of the present disclosure also relates to a manufacturing method thereof.
[0168] The blended yarn of recycled carbon fiber and thermoplastic resin fiber according to the second invention of the present disclosure is: The recycled carbon fiber has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more; and The recycled carbon fiber contains a residual carbon component, and the content of the residual carbon component is more than 0% by weight and 5.0% by weight or less based on the recycled carbon fiber; It is characterized by:
[0169] The blended yarn according to the second invention of the present disclosure can be produced by a general spinning method. This spinning method may include the steps of carding, drawing, and roving. Here, the carding step may be a step of separating and opening a discontinuous fiber aggregate and orienting the mixed single fibers in one direction to produce a thick sliver, the drawing step may be a step of doubling several slivers and stretching the yarn to further improve the fiber orientation, and the roving step may be a step of further stretching the sliver and twisting it to wind up the blended yarn.
[0170] The tensile strength of a sliver is determined by frictional forces caused by contact or entanglement between single fibers, so the tensile strength is improved by opening each fiber well and increasing the contact area or entanglement between single fibers, and the decrease in tensile strength can be suppressed by suppressing breakage of single fibers and not increasing the number of joints between single fibers. Increasing the twist also increases the contact area between single fibers, improving the tensile strength. To compensate for the frictional force, an oil agent may be applied to each fiber or the sliver as necessary.
[0171] Generally, carbon fibers are characterized by having no crimping property and high surface smoothness, which results in weak entanglement between single fibers, and furthermore, because they are hard with a high elastic modulus and low elongation, they are relatively prone to breaking and breaking. The thermoplastic resin fiber blended with the recycled carbon fiber has the effect of increasing the entanglement between the single fibers, and even blending a small amount of thermoplastic resin fiber can greatly improve the tensile strength of the sliver.
[0172] Without intending to be limited by theory, it is believed that the blended yarn related to the second invention of the present disclosure has a high Weibull shape coefficient for the single fiber tensile strength of the recycled carbon fiber, and therefore the variation in tensile strength is small. Compared to general virgin carbon fiber with the same tensile strength, there are relatively few single fibers with low tensile strength, and therefore single fiber breakage of the recycled carbon fiber is relatively suppressed.
[0173] Moreover, general characteristics of recycled carbon fibers obtained by the method of decomposition through heat treatment include that the tensile strength is easily reduced due to the generation of oxidation defects in the recycled carbon fibers, and that carbides of the resin components may be contained in the recycled carbon fibers as residual carbon components. The residual carbon components may strongly bond the single fibers of the recycled carbon fibers together. In the production of spun yarn, the residual carbon components are thought to hinder the opening in the carding process and the entanglement of the single fibers together.
[0174] Without intending to be limited by theory, the blended yarn according to the second invention of the present disclosure is made from recycled carbon fibers having a relatively low content of residual carbon components, and therefore, entanglement of the single fibers is easily achieved.
[0175] For the reasons mentioned above, it is believed that the blended yarn according to the second invention of the present disclosure is likely to have sufficient tensile strength for stable production without yarn loss due to the tension in the spinning process, since frictional force is easily obtained due to the entanglement of single fibers.
[0176] The second invention of the present disclosure also includes a carbon fiber reinforced thermoplastic resin pellet having the above-mentioned blended yarn. The carbon fiber reinforced thermoplastic resin pellet is Having a core-sheath structure; The blended yarn is the core component; and The sheath component is a thermoplastic resin; It is characterized by:
[0177] The carbon fiber reinforced thermoplastic resin pellet according to the second invention of the present disclosure can be produced by cutting a resin strand obtained by coating a blended yarn with a thermoplastic resin in the same manner as in the production method of a general long fiber reinforced pellet, except that the blended yarn according to the second invention of the present disclosure is used as a substitute for continuous carbon fiber, and therefore can contain recycled carbon fibers having a relatively long fiber length compared to short fiber reinforced pellets produced by cutting a resin strand in which discontinuous carbon fibers are kneaded and dispersed in a thermoplastic resin. That is, the carbon fiber reinforced thermoplastic resin pellet according to the second invention of the present disclosure can be supplied to an injection molding machine or the like to produce a carbon fiber-containing product having excellent mechanical properties.
[0178] The second invention according to the present disclosure will be described in further detail below.
[0179] <Recycled carbon fiber> Recycled carbon fibers (recycled carbon fibers) contain carbon fiber components and carbon components other than the carbon fiber components (particularly residual carbon components). In recycled carbon fibers, the carbon components other than the carbon fiber components are usually attached to the surface of the carbon fiber components.
[0180] The recycled carbon fiber according to the second invention of the present disclosure is characterized in that it has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more, and contains residual carbon components, the content of which is more than 0% and not more than 5.0% by weight of the recycled carbon fiber.
[0181] As long as the recycled carbon fiber has the above characteristics, the recycling method is not particularly limited, but it may be, for example, recycled carbon fiber obtained by heat treating a carbon fiber-containing plastic product such as carbon fiber reinforced plastic (CFRP).
[0182] Particularly preferably, the recycled carbon fiber is a recycled carbon fiber obtained by a semiconductor thermal activation method. That is, a particularly preferred embodiment of the present disclosure includes a recycled carbon fiber produced by decomposing a plastic component contained in a carbon fiber-containing plastic product by a semiconductor thermal activation method.
[0183] The "thermal activation of semiconductors" (TASC) method is a method for decomposing compounds such as polymers by utilizing the thermal activation of semiconductors (TASC).
[0184] For a method for obtaining recycled carbon fibers having the properties according to the second invention of the present disclosure using the semiconductor thermal activation method, the above description of the first invention can be referred to. That is, by using the above decomposition method according to the first invention to recover carbon fibers from a plastic-containing material containing plastics and carbon fibers, recycled carbon fibers having the properties according to the second invention of the present disclosure (as well as the third and fourth inventions described below) can be obtained.
[0185] <Single fiber tensile strength> The single fiber tensile strength is preferably 3.1 GPa or more, 3.2 GPa or more, 3.3 GPa or more, or 3.4 GPa or more. The upper limit of the single fiber tensile strength is not particularly limited, but may be 6.0 GPa or less.
[0186] The single fiber tensile strength can be measured according to JIS R7606 as described above in relation to the first invention:
[0187] <Weibull shape factor> The Weibull shape coefficient is preferably 6.5 or more, 7.0 or more, 7.5 or more, 8.0 or more, or 8.5 or more. The upper limit of the Weibull shape coefficient is not particularly limited, but may be 15.0 or less. A high Weibull shape coefficient of single fiber tensile strength means that the variation in single fiber tensile strength is small.
[0188] The Weibull shape factor can be calculated as described above in relation to the first invention.
[0189] <Carbon fiber component> The carbon fiber component in the recycled carbon fiber is usually derived from the carbon fiber contained in the carbon fiber-containing product that was the raw material for the recycled carbon fiber. The carbon fiber component in the recycled carbon fiber may be modified by being subjected to a heat treatment or the like during the production process of the recycled carbon fiber.
[0190] The carbon fiber component in the recycled carbon fiber may be, for example, a PAN-based carbon fiber or a pitch-based carbon fiber.
[0191] The form of the carbon fiber component in the recycled carbon fiber is not particularly limited, but may be a form of a carbon fiber bundle composed of a plurality of single threads (single fibers, filaments). The number of filaments constituting the carbon fiber bundle may be in the range of 1,000 to 80,000, or 3,000 to 50,000. The diameter of the filaments constituting the carbon fiber component in the recycled carbon fiber may be 0.1 μm to 30 μm, 1 μm to 10 μm, or 3 μm to 8 μm.
[0192] <Residual carbon components> The residual carbon component contained in the recycled carbon fibers is, in particular, residual carbon derived from the resin contained in the carbon fiber-containing plastic product used as a raw material in producing the recycled carbon fibers.
[0193] In the second invention of the present disclosure, the residual carbon component is more than 0% by weight and 5.0% by weight or less with respect to the recycled carbon fiber. In this case, a blended yarn having improved resistance to yarn slippage due to the tension in the spinning process can be obtained.
[0194] Furthermore, when the residual carbon component is more than 0% by weight and not more than 5.0% by weight, contamination caused by a relatively large amount of carbon components (especially charcoal) can be avoided, and the carbon components that may become foreign matter when producing carbon fiber-containing products, etc. using the blended yarn as a material can be reduced.
[0195] Preferably, the residual carbon component is 4.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less relative to the recycled carbon fiber. It is preferable that the residual carbon component is as low as possible, but it may be 0.01% by weight or more, 0.1% by weight or more, 0.2% by weight or more, 0.4% by weight or more, 0.6% by weight or more, 0.8% by weight or more, 1.0% by weight or more, or 1.2% by weight or more relative to the carbon fiber.
[0196] The content of the residual carbon component in the recycled carbon fiber can be measured by thermogravimetric analysis (TGA) as described above in relation to the first invention.
[0197] <Thermoplastic resin fiber> Examples of the thermoplastic resin fibers contained in the blended yarn according to the second aspect of the present disclosure include polyolefin resin fibers (e.g., polypropylene resin fibers and polyethylene resin fibers), polyester resin fibers (e.g., polyethylene terephthalate resin fibers, polybutylene terephthalate resin fibers, and polylactic acid resin fibers), polyamide resin fibers, polyether ketone resin fibers, polycarbonate resin fibers, phenoxy resin fibers, and polyphenylene sulfide resin fibers. The thermoplastic resin fibers may be of one type only, or may be a mixture of two or more types of thermoplastic resin fibers.
[0198] <Blended yarn> The blended yarn according to the second aspect of the present invention is a spun yarn containing recycled carbon fiber and thermoplastic resin fiber. The blended yarn may contain, for example, a binder or the like that is added to the recycled carbon fiber. The blended yarn may also be a spun yarn that is substantially composed of recycled carbon fiber and thermoplastic resin fiber.
[0199] <Recycled carbon fiber content> The content of recycled carbon fibers in the blended yarn according to the second aspect of the present invention is preferably more than 50% by weight and not more than 98% by weight, based on the weight of the blended yarn. Particularly preferably, it may be more than 55% by weight, more than 60% by weight, more than 65% by weight, or more than 70% by weight, and / or may be not more than 97% by weight, not more than 96% by weight, not more than 95% by weight, not more than 94% by weight, not more than 93% by weight, not more than 92% by weight, not more than 91% by weight, or not more than 90% by weight.
[0200] If the recycled carbon fiber content is more than 50% by weight, when the recycled carbon fiber is used to produce the carbon fiber reinforced thermoplastic resin pellets according to the present disclosure, it is not necessary to reduce the amount of thermoplastic resin coating in order to increase the carbon fiber content, and the stability of the coating process is improved. If the recycled carbon fiber content is 98% by weight or less, the entanglement with the thermoplastic resin fiber to be mixed is sufficient, and the yarn is less likely to come off due to the tension in the spinning process.
[0201] The content of thermoplastic resin fibers in the blended yarn according to the second aspect of the present invention may be 50% by weight or less, 40% by weight or less, or 30% by weight or less, and / or may be more than 3% by weight, more than 4% by weight, more than 5% by weight, more than 6% by weight, more than 7% by weight, more than 8% by weight, more than 9% by weight, or more than 10% by weight, based on the weight of the blended yarn.
[0202] <Average fiber length> The recycled carbon fibers contained in the blended yarn according to the second aspect of the present invention can have an average length of 20 mm or more and 80 mm or less. Fibers having a length in this range can be obtained, for example, by cutting fibers having a relatively long dimension. The average length of the recycled carbon fibers can be 20 mm or more, 30 mm or more, or 40 mm or more, and / or 80 mm or less, 70 mm or less, or 60 mm or less.
[0203] The thermoplastic resin fibers contained in the blended yarn according to the second aspect of the present invention can have an average length of 20 mm or more and 80 mm or less. Fibers having a length in this range can be obtained, for example, by cutting fibers having a relatively long dimension. The average length of the thermoplastic resin fibers can be 20 mm or more, 30 mm or more, or 40 mm or more, and / or 80 mm or less, 70 mm or less, or 60 mm or less.
[0204] In the production of the blended yarn according to the second aspect of the present invention, when the average length of the recycled carbon fiber and the thermoplastic resin fiber is 20 mm or more, the yarn pull-out resistance against the tension in the spinning process of the sliver can be improved. When the average length of the recycled carbon fiber and the thermoplastic resin fiber is 80 mm or less, the winding around the manufacturing equipment parts can be reduced.
[0205] The average length of the recycled carbon fibers and thermoplastic resin fibers can be calculated by measuring the lengths of 50 fibers visually using calipers or in images taken with a digital camera or optical microscope, and averaging the measured values.
[0206] <Method of manufacturing blended yarn> As described above, the blended yarn of recycled carbon fiber and thermoplastic resin fiber according to the second invention of the present disclosure can be manufactured by a general spinning method. That is, the manufacturing method of the blended yarn according to the second invention of the present disclosure may include a carding process in which discontinuous fiber aggregates are separated and opened, and the mixed single fibers are oriented in one direction to manufacture a thick sliver, a drawing process in which several slivers are combined and stretched to further improve the degree of fiber orientation, and a roving process in which the sliver is further stretched and twisted to wind up the blended yarn.
[0207] When producing the blended yarn according to the second aspect of the present invention, a binder can be applied. The binder has a role of promoting the binding of the recycled carbon fiber to the thermoplastic resin fiber in particular. The timing of applying the binder is not particularly limited, but the binder may be applied directly to the recycled carbon fiber, or to the blended yarn containing the recycled carbon fiber and the thermoplastic resin fiber. The binder may be, for example, an epoxy resin. The method of applying the binder is not particularly limited, and a known method can be used. For example, the binder can be applied by immersing the recycled carbon fiber or the blended yarn in a solution or dispersion of the binder and drying it. The amount of the binder may be 0.1% by weight to 25% by weight, or 1% by weight to 20% by weight, based on the recycled carbon fiber.
[0208] <Carbon fiber reinforced thermoplastic resin pellets> According to the second invention of the present disclosure, there is provided a carbon fiber reinforced thermoplastic resin pellet having a core-sheath structure, in which the blended yarn according to the second invention of the present disclosure is the core component and the thermoplastic resin is the sheath component. The pellet according to the second invention of the present disclosure contains recycled carbon fibers having a relatively long fiber length compared to short fiber reinforced pellets obtained by kneading and dispersing recycled carbon fibers in a thermoplastic resin, and therefore, by supplying the pellet to an injection molding machine or the like, a carbon fiber-containing product having excellent mechanical properties can be manufactured.
[0209] <Method of manufacturing carbon fiber reinforced thermoplastic resin pellets> The carbon fiber reinforced thermoplastic resin pellets having a core-sheath structure according to the second invention of the present disclosure can be produced by a method including producing a carbon fiber reinforced thermoplastic resin strand by coating the blended yarn with a thermoplastic resin and cutting the strand, and more specifically, as described above, the pellets can be produced by cutting a resin strand coated with a thermoplastic resin in the same manner as in the general method for producing long fiber reinforced pellets, except that the blended yarn according to the second invention of the present disclosure is used instead of continuous carbon fiber. That is, the pellets can be produced by a method including a coating step in which the blended yarn, which is continuously transported while being rewound, is threaded through a die to which molten thermoplastic resin is continuously supplied from a supply port separate from the blended yarn, and a cutting step in which the carbon fiber reinforced thermoplastic resin strand discharged from the die is cooled and then cut.
[0210] <Thermoplastic resin> Thermoplastic resins used in the coating process in the production of the pellets according to the second aspect of the present invention (i.e., thermoplastic resins constituting the sheath component of the pellets) include polyolefin resins (e.g., polypropylene resins and polyethylene resins), polyester resins (e.g., polyethylene terephthalate resins, polybutylene terephthalate resins, and polylactic acid resins), polyamide resins, polyether ketone resins, polycarbonate resins, phenoxy resins, and polyphenylene sulfide resins. The thermoplastic resin may be one type only, or may be a mixture of two or more types of thermoplastic resins.
[0211] In addition, the thermoplastic resin constituting the sheath component of the pellet according to the second aspect of the present disclosure may be the same type as the thermoplastic resin fiber contained in the blended yarn according to the second aspect of the present disclosure, or may be a different type. In particular, it is preferable that the melting point (T0 (°C)) of the thermoplastic resin constituting the sheath component of the pellet is more than 10 (°C) lower than the melting point (T1 (°C)) of the thermoplastic resin fiber contained in the blended yarn according to the present disclosure. In this case, when producing the carbon fiber reinforced thermoplastic resin pellet according to the present disclosure, it is possible to suppress the melting of the thermoplastic resin fiber contained in the blended yarn, and it is easy to set the production conditions in which only the thermoplastic resin covering the blended yarn melts, so that the blended yarn can be stably threaded through the die. The upper limit of the difference (T1-T0) between T1 and T0 is not particularly limited, but may be, for example, 200 (°C) or less, 150 (°C) or less, 100 (°C) or less, or 50 (°C) or less.
[0212] Furthermore, the above-mentioned thermoplastic resin used in the coating treatment may be blended with various polymers, fillers, stabilizers, pigments, etc., for the purpose of improving fluidity, external gloss, flame retardancy, thermal stability, weather resistance, impact resistance, etc., within the scope of not impairing the mechanical strength.
[0213] <Pellet core-sheath structure> The carbon fiber reinforced thermoplastic resin pellets according to the second invention of the present disclosure are produced by cutting (slicing) the carbon fiber reinforced thermoplastic resin strands obtained by coating the blended yarn according to the second invention of the present disclosure with a thermoplastic resin, so that the blended yarn constitutes the core component and the thermoplastic resin constitutes the sheath component.
[0214] Regarding the proportion of the thermoplastic resin as the sheath component in the carbon fiber reinforced thermoplastic resin pellets having a core-sheath structure, the thermoplastic resin as the sheath component is preferably 50 parts by weight to 1000 parts by weight, more preferably 100 parts by weight to 750 parts by weight, and most preferably 250 parts by weight to 500 parts by weight, per 100 parts by weight of the recycled carbon fiber contained in the blended yarn.
[0215] <Pellet cut length> The cut length of the pellet according to the second aspect of the present invention is preferably 3 mm or more and 10 mm or less. It may be particularly preferably 5 mm or less. The cut length of the pellet particularly corresponds to the length of the core structure of the pellet in the axial direction.
[0216] If the cut length of the pellets is 3 mm or more, the average length of the recycled carbon fibers will be relatively long, and the mechanical properties of the carbon fiber-containing product made from the pellets as a molding raw material can be further improved. If the cut length of the pellets is 10 mm or less, the recycled carbon fibers will be easily dispersed during molding, and the mechanical properties of the carbon fiber-containing product can be further improved.
[0217] The diameter of the core-sheath type pellet is not particularly limited, but may be 1 / 10 to 2 times the cut length of the pellet, and is preferably 1 / 4 to 1 time the cut length of the pellet. If the diameter of the pellet is too small, some parts may not be covered. Conversely, if the diameter of the pellet is too large, the pellet may not fit into the molding machine properly, making molding difficult.
[0218] The cut length and diameter of the pellets can be calculated by measuring the cut length or diameter of 30 or more pellets visually using a caliper or the like, or in images taken with a digital camera or optical microscope, and averaging the measured values.
[0219] FIG. 6 is a schematic diagram showing a sheath-core carbon fiber reinforced thermoplastic resin pellet 200 according to the second invention of the present disclosure. The diagram is a schematic diagram for explanation and is not drawn to scale. The sheath-core pellet 200 has a core component 210 and a sheath component 220. The pellet 200 also has a cut length L and a diameter R. The sheath-core pellet 200 can be produced by cutting (cutting process, "C" in FIG. 6) a sheath-core carbon fiber reinforced thermoplastic resin strand 100 having a core component 110 made of blended yarn and a sheath component 120 made of thermoplastic resin.
[0220] (The Third Invention) The third invention of the present disclosure relates to a carbon fiber reinforced thermoplastic resin strand including a blended yarn of recycled carbon fiber and thermoplastic resin fiber suitable for three-dimensional modeling, and a manufacturing method thereof.
[0221] The carbon fiber reinforced thermoplastic resin strand according to the third aspect of the present disclosure has a blended yarn containing recycled carbon fiber and thermoplastic resin fiber. The blended yarn of recycled carbon fiber and thermoplastic resin fiber is: The recycled carbon fiber has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more; and The recycled carbon fiber contains a residual carbon component, and the content of the residual carbon component is more than 0% by weight and 5.0% by weight or less with respect to the recycled carbon fiber; It is characterized by:
[0222] In one embodiment according to the third invention of the present disclosure, a carbon fiber reinforced thermoplastic resin strand is made of the above blended yarn.
[0223] The blended yarn according to the third invention of the present disclosure is produced by a general spinning method, which may include carding, drawing, and roving steps. For each of these steps, reference may be made to the above description of the second invention.
[0224] The tensile strength of a sliver is determined by frictional forces caused by contact or entanglement between single fibers, so the tensile strength is improved by opening each fiber well and increasing the contact area or entanglement between single fibers, and the decrease in tensile strength can be suppressed by suppressing single fiber breakage and not increasing the number of joints between single fibers. Increasing the twist also increases the contact area between single fibers, improving the tensile strength. To compensate for the frictional force, an oil agent may be applied to each fiber or the sliver as necessary.
[0225] Generally, carbon fibers are characterized by having no crimping property and high surface smoothness, which results in weak entanglement between single fibers, and furthermore, because they are hard with a high elastic modulus and low elongation, they are relatively prone to breaking and breaking. The thermoplastic resin fiber blended with the recycled carbon fiber has the effect of increasing the entanglement between the single fibers, and even blending a small amount of thermoplastic resin fiber can greatly improve the tensile strength of the sliver.
[0226] Without intending to be limited by theory, it is believed that the blended yarn according to the third invention of the present disclosure has a high Weibull shape coefficient for the single fiber tensile strength of the recycled carbon fiber, and therefore the variation in tensile strength is small. Compared to general virgin carbon fiber with the same tensile strength, there are fewer single fibers with low tensile strength, and therefore single fiber breakage of the recycled carbon fiber is relatively suppressed.
[0227] Moreover, general characteristics of recycled carbon fibers obtained by the method of decomposition through heat treatment include that the tensile strength is easily reduced due to the generation of oxidation defects in the recycled carbon fibers, and that carbides of the resin components may be contained in the recycled carbon fibers as residual carbon components. The residual carbon components may strongly bond the single fibers of the recycled carbon fibers together. In the production of spun yarn, the residual carbon components are thought to hinder the opening in the carding process and the entanglement of the single fibers together.
[0228] Without intending to be limited by theory, the blended yarn according to the third invention of the present disclosure is made from recycled carbon fibers with a low content of residual carbon components, and therefore single fibers are more likely to become entangled with each other.
[0229] For the reasons mentioned above, it is believed that the blended yarn according to the third invention of the present disclosure is likely to have sufficient tensile strength for stable production without yarn loss due to the tension in the spinning process, since frictional force is easily obtained due to the entanglement of single fibers.
[0230] In one embodiment according to the third invention of the present disclosure, the carbon fiber reinforced thermoplastic resin strand has a core-sheath structure, The blended yarn is a core component, and the thermoplastic resin is a sheath component. It is characterized by:
[0231] The carbon fiber reinforced thermoplastic resin strand having a core-sheath structure according to one embodiment of the third invention of the present disclosure can be produced by coating the blended yarn with a thermoplastic resin in the same manner as in the production method of a general long-fiber reinforced strand, except that the blended yarn according to the third invention of the present disclosure is used as a substitute for continuous carbon fiber, and therefore can contain recycled carbon fibers having a relatively long fiber length compared to short-fiber reinforced thermoplastic resin strands in which discontinuous carbon fibers are kneaded and dispersed in a thermoplastic resin. That is, the carbon fiber reinforced thermoplastic resin strand according to the third invention of the present disclosure can be supplied to an injection molding machine or the like or a three-dimensional modeling device or the like to produce a carbon fiber-containing product having excellent mechanical properties.
[0232] The third invention of the present disclosure will be described in further detail below.
[0233] <Recycled carbon fibers, etc.> For details of recycled carbon fibers, single fiber tensile strength, Weibull shape coefficient, carbon fiber components in recycled carbon fibers, and residual carbon components contained in recycled carbon fibers, please refer to the corresponding descriptions in the second present invention above.
[0234] <Thermoplastic resin fiber> For the thermoplastic resin fibers contained in the blended yarn according to the third invention of the present disclosure, reference may be made to the description of the thermoplastic resin fibers according to the second invention of the present disclosure.
[0235] <Blended yarn> The blended yarn according to the third aspect of the present invention is a spun yarn containing recycled carbon fiber and thermoplastic resin fiber. The blended yarn may also contain, for example, a binder that is added to the recycled carbon fiber. In particular, the blended yarn is a spun yarn that is substantially composed of recycled carbon fiber and thermoplastic resin fiber.
[0236] <Recycled carbon fiber and thermoplastic resin fiber content> For the contents of recycled carbon fiber and thermoplastic resin fiber contained in the blended yarn according to the third invention, reference may be made to the corresponding descriptions in the above second invention.
[0237] <Average fiber length> For the average length of the recycled carbon fibers and thermoplastic resin fibers contained in the blended yarn according to the third invention of the present disclosure, reference may be made to the corresponding description above regarding the second invention.
[0238] <Method of manufacturing blended yarn> As described above, the blended yarn of recycled carbon fiber and thermoplastic resin fiber according to the third aspect of the present disclosure can be produced by a general spinning method. For the production method, the above description of the production method of the blended yarn according to the second aspect of the present invention can be referred to.
[0239] When producing the blended yarn, a binder can be applied, for which reference can be made to the corresponding description above regarding the second invention.
[0240] <Carbon fiber reinforced thermoplastic resin strand with core-sheath structure> According to one embodiment of the third invention of the present disclosure, the above blended yarn according to the third invention of the present disclosure is coated with a thermoplastic resin to provide a carbon fiber-reinforced thermoplastic resin strand having a core-sheath structure in which the blended yarn is a core component and the thermoplastic resin is a sheath component. This strand contains recycled carbon fibers having a relatively long fiber length compared to short fiber reinforced strands obtained by kneading and dispersing recycled carbon fibers in a thermoplastic resin, and therefore, by supplying the strand to a three-dimensional modeling device or the like, a carbon fiber-containing product having particularly excellent mechanical properties and the like can be manufactured.
[0241] <Manufacturing method of carbon fiber reinforced thermoplastic resin strand with core-sheath structure> The carbon fiber reinforced thermoplastic resin strand having a core-sheath structure according to one embodiment of the third invention of the present disclosure can be produced by coating the blended yarn with a thermoplastic resin, and more specifically, as described above, can be produced by coating the blended yarn with a thermoplastic resin in the same manner as in the general method for producing a long fiber reinforced strand, except that the blended yarn according to the third invention of the present disclosure is used instead of the continuous carbon fiber. That is, the strand can be produced by a method including a coating step in which the blended yarn, which is continuously transported while being rewound, is threaded through a die through which molten thermoplastic resin is continuously supplied from a supply port separate from the blended yarn, and a discharge step in which the resin is discharged from the die.
[0242] <Thermoplastic resin> Examples of the thermoplastic resin used in the coating process in the production of the carbon fiber reinforced thermoplastic resin strand (i.e., the thermoplastic resin that becomes the sheath component of the carbon fiber reinforced thermoplastic resin strand having a core-sheath structure) include polyolefin resins (e.g., polypropylene resins and polyethylene resins), polyester resins (e.g., polyethylene terephthalate resins, polybutylene terephthalate resins, and polylactic acid resins), polyamide resins, polyether ketone resins, polycarbonate resins, phenoxy resins, and polyphenylene sulfide resins. The thermoplastic resin may be one type only, or may be a mixture of two or more types of thermoplastic resins.
[0243] In addition, the thermoplastic resin that is the sheath component of the carbon fiber reinforced thermoplastic resin strand may be the same type as the above-mentioned thermoplastic resin fiber contained in the blended yarn according to the third invention of the present disclosure, or may be a different type. In particular, when the melting point T0 (°C) of the thermoplastic resin that is the sheath component of the carbon fiber reinforced thermoplastic resin strand is lower than the melting point of the thermoplastic resin fiber T1 (°C) contained in the blended yarn according to the third invention of the present disclosure (particularly when T1-T0>10 (°C)), when producing the carbon fiber reinforced thermoplastic resin strand according to the third invention of the present disclosure, the blended yarn can be covered with a thermoplastic resin melted at a temperature lower than the melting point of the thermoplastic resin fiber contained in the blended yarn, so that the blended yarn can be stably threaded through the die. The upper limit of the difference (T1-T0) between T1 and T0 is not particularly limited, but may be, for example, 200 (°C) or less, 150 (°C) or less, 100 (°C) or less, or 50 (°C) or less.
[0244] Furthermore, the above-mentioned thermoplastic resin used in the coating treatment may be blended with various polymers, fillers, stabilizers, pigments, etc., for the purpose of improving fluidity, external gloss, flame retardancy, thermal stability, weather resistance, impact resistance, etc., within the scope of not impairing the mechanical strength.
[0245] <Strand core-sheath structure> The carbon fiber reinforced thermoplastic resin strand according to one embodiment of the third invention of the present disclosure is produced by coating the above-mentioned blended yarn according to the third invention of the present disclosure with a thermoplastic resin, so that the blended yarn serves as the core component and the thermoplastic resin serves as the sheath component.
[0246] The carbon fiber reinforced thermoplastic resin strand according to the third aspect of the present disclosure is particularly suitable for the production of three-dimensional objects. From the viewpoint of the stability of the three-dimensional objects, the average diameter of the strand is preferably 0.7 mm or more and 2.2 mm or less, and more preferably 1.0 mm or more and 2.0 mm or less.
[0247] FIG. 7 is a schematic diagram of a carbon fiber reinforced thermoplastic resin strand 100b according to the third invention of the present disclosure. The drawing is a schematic diagram for explanation and is not to scale. The strand 100b in FIG. 7 has a core-sheath structure, and has a core component 110b made of blended yarn and a sheath component 120b made of thermoplastic resin.
[0248] Regarding the proportion of the thermoplastic resin as the sheath component in the carbon fiber reinforced thermoplastic resin strand having a core-sheath structure, the thermoplastic resin as the sheath component is preferably 50 parts by weight to 1000 parts by weight, more preferably 100 parts by weight to 750 parts by weight, and most preferably 250 parts by weight to 500 parts by weight, per 100 parts by weight of the recycled carbon fiber contained in the blended yarn.
[0249] ≪3D object≫ A third invention of the present disclosure includes a method for producing a three-dimensional object by a fused deposition modeling process using the carbon fiber reinforced thermoplastic resin strand according to the third invention of the present disclosure.
[0250] In three-dimensional modeling, a three-dimensional model is created by sequentially layering resin on each cross section of an object cut along multiple parallel planes, to generate a three-dimensional model of the object. Such three-dimensional models can be used, for example, for prototyping parts and manufacturing products. As a method for three-dimensional modeling, a molten deposition method in which resin is melted and deposited can be used in particular.
[0251] The method for producing a three-dimensional object according to the third invention of the present disclosure can be performed according to a known melt deposition method, except that the carbon fiber reinforced thermoplastic resin strand according to the third invention of the present disclosure is used.
[0252] Specifically, for example, the carbon fiber reinforced thermoplastic resin strand according to the third invention of the present disclosure is supplied to the discharge head of a molten deposition three-dimensional modeling device, the carbon fiber reinforced thermoplastic resin strand is melted in the discharge head, and the molten carbon fiber reinforced thermoplastic resin strand is discharged from the discharge head and deposited in layers, repeatedly to produce a three-dimensional object.
[0253] (Fourth Invention) A fourth invention of the present disclosure relates to carbon fiber reinforced thermoplastic resin pellets containing recycled carbon fibers produced using waste materials of carbon fiber reinforced resin moldings or the like.
[0254] The carbon fiber reinforced thermoplastic resin pellet according to the fourth invention of the present disclosure contains recycled carbon fibers and a thermoplastic resin, This recycled carbon fiber, It has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more, and Contains residual carbon components, and the content of the residual carbon components is more than 0% by weight and 5.0% by weight or less based on the recycled carbon fiber; It is characterized by:
[0255] Generally, carbon fiber reinforced thermoplastic resin pellets are obtained by melt-kneading thermoplastic resin and carbon fiber in a twin-screw extruder or the like, but the carbon fiber may be crushed in the extruder due to the high shear applied during kneading. If the average fiber length of the carbon fiber in the obtained pellets is less than 300 μm, the mechanical property reinforcing effect may decrease.
[0256] Without intending to be limited by theory, it is believed that the recycled carbon fiber according to the fourth invention of the present disclosure has a high Weibull shape coefficient for single fiber tensile strength, and therefore the variation in tensile strength is small. Compared to general unused carbon fibers with equivalent tensile strength, there are fewer single fibers with low tensile strength, and therefore single fiber breakage of the recycled carbon fiber is relatively suppressed.
[0257] Furthermore, in general, when the tensile strength of the carbon fibers fed into the extruder varies greatly, the low-strength fibers are crushed finer, resulting in a relatively large proportion of carbon fibers of 300 μm or less remaining in the pellets. On the other hand, as described above, the recycled carbon fibers of the present invention have a high Weibull shape coefficient and therefore a small variation in tensile strength, so the proportion of fibers crushed to 300 μm or less is small, and as a result, it is believed that a large mechanical property reinforcement effect can be obtained.
[0258] In particular, a carbon fiber aggregate can be used as a source of recycled carbon fiber when producing the pellet according to the fourth invention of the present disclosure. The carbon fiber aggregate includes recycled carbon fiber and a binder. For the production method thereof, reference can be made to, for example, the descriptions in Japanese Patent No. 3452363 and Japanese Patent Laid-Open No. 2020-180421.
[0259] The fourth aspect of the present disclosure will now be described in further detail.
[0260] <Recycled carbon fiber> With regard to the recycled carbon fiber, reference may be made to the above description regarding the recycled carbon fiber according to the second invention.
[0261] <Average remaining fiber length> Preferably, the remaining average fiber length of the recycled carbon fibers in the carbon fiber reinforced thermoplastic resin pellets (i.e., the average fiber length of the recycled carbon fibers present in the pellets) is 300 μm or more. The remaining average fiber length of the recycled carbon fibers is more preferably 320 μm or more, 330 μm or more, or 340 μm or more. The upper limit of the remaining average fiber length of the recycled carbon fibers is not particularly limited, but may be 600 μm or less, or 500 μm or less.
[0262] The remaining average fiber length of the recycled carbon fibers in the carbon fiber reinforced thermoplastic pellets can be calculated as the number average by removing the base matrix resin in the pellets by sulfuric acid decomposition, filtering the pellets, and then measuring the fiber lengths of 300 or more single fibers using a microscope.
[0263] <Frequency of single fibers of 300 μm or less> Regarding the recycled carbon fibers in the carbon fiber reinforced thermoplastic resin pellets, the frequency of single fibers of 300 μm or less (particularly less than 300 μm) is preferably 40% or less. The frequency of single fibers of 300 μm or less (particularly less than 300 μm) is particularly preferably 39% or less, 38% or less, 37% or less, or 36% or less. The lower limit of the frequency of single fibers of 300 μm or less is not particularly limited, but may be, for example, 1% or more, or 10% or more.
[0264] The frequency of occurrence of single fibers of 300 μm or less (or less than 300 μm) can be obtained by measuring the fiber length of single fibers in the same manner as in the measurement of the remaining average fiber length described above, and calculating the proportion of the number of fibers of 300 μm or less (or less than 300 μm).
[0265] <Single fiber tensile strength, etc.> For the single fiber tensile strength, the Weibull shape coefficient, and the carbon fiber components in the recycled carbon fibers, reference may be made to the corresponding descriptions in the above second invention.
[0266] <Residual carbon components> The residual carbon component contained in the recycled carbon fibers is, in particular, residual carbon derived from the resin contained in the carbon fiber-containing plastic product used as a raw material in producing the recycled carbon fibers.
[0267] Preferably, the residual carbon component is 4.0% by weight or less, 3.0% by weight or less, or 2.0% by weight or less relative to the recycled carbon fiber. It is preferable that the residual carbon component is as low as possible, but it may be 0.01% by weight or more, 0.1% by weight or more, 0.2% by weight or more, 0.4% by weight or more, 0.6% by weight or more, 0.8% by weight or more, 1.0% by weight or more, or 1.2% by weight or more relative to the carbon fiber.
[0268] The content of the residual carbon component in the recycled carbon fiber can be measured by thermogravimetric analysis (TGA) as described above in relation to the first invention.
[0269] <Thermoplastic resin> Examples of the thermoplastic resin contained in the carbon fiber reinforced thermoplastic resin pellet according to the fourth invention of the present disclosure include polyolefin resins (e.g., polypropylene resins and polyethylene resins), polyester resins (e.g., polyethylene terephthalate resins, polybutylene terephthalate resins, and polylactic acid resins), polyamide resins, polyether ketone resins, polycarbonate resins, phenoxy resins, and polyphenylene sulfide resins. The thermoplastic resin may be one type only, or may be a mixture of two or more types of thermoplastic resins.
[0270] <Pellet> The carbon fiber reinforced thermoplastic resin pellet according to a fourth invention of the present disclosure contains recycled carbon fibers and a thermoplastic resin.
[0271] The shape of the carbon fiber reinforced thermoplastic resin pellet according to the fourth invention of the present disclosure is not particularly limited, but the length of the pellet in the longitudinal direction is preferably 3 mm or more and 10 mm or less, and particularly preferably 5 mm or less.
[0272] (Recycled carbon fiber content) The recycled carbon fiber content in the carbon fiber reinforced thermoplastic pellets according to the fourth invention of the present disclosure is preferably less than 50% by weight, 40% by weight or less, 30% by weight or less, and / or 5% by weight or more, 7% by weight or more, or 8% by weight or more, relative to the carbon fiber reinforced thermoplastic resin pellets.
[0273] If the content of the recycled carbon fibers is less than 50% by weight of the carbon fiber reinforced thermoplastic resin pellets, the carbon fibers can be particularly uniformly dispersed in the pellets. If the content of the recycled carbon fibers is 5% by weight or more of the carbon fiber reinforced thermoplastic resin pellets, a particularly good mechanical property reinforcing effect of the pellets can be obtained.
[0274] <Pellet manufacturing method> The method for producing the carbon fiber reinforced thermoplastic resin pellets according to the fourth aspect of the present disclosure is not particularly limited, but the pellets can be obtained, for example, by a production method including the following: Providing recycled carbon fiber; Providing a thermoplastic resin; and Kneading recycled carbon fibers with molten thermoplastic resin; Where: The recycled carbon fiber has a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more, and The recycled carbon fibers contain residual carbon components, and the content of the residual carbon components is more than 0% by weight and not more than 5.0% by weight based on the weight of the recycled carbon fibers.
[0275] For the recycled carbon fibers and thermoplastic resin used in the production of the carbon fiber reinforced thermoplastic resin pellets according to the fourth invention of the present disclosure, the above description of the carbon fiber reinforced thermoplastic resin pellets according to the fourth invention of the present disclosure can be referred to. The kneading method is not particularly limited, and can be performed by a known method.
[0276] In one exemplary embodiment for producing carbon fiber reinforced thermoplastic resin pellets according to the fourth invention of the present disclosure, a thermoplastic resin that serves as a base resin is supplied via a main feeder of a twin-screw kneading extruder, recycled carbon fiber is supplied from the twin-screw feeder to the resin that has been kneaded and melted in the extruder, and the extruded mixture is cooled in a water-cooled bath and then cut to obtain carbon fiber reinforced thermoplastic resin pellets.
[0277] ≪Molded products≫ A molded article can be produced by molding the carbon fiber reinforced thermoplastic resin pellets according to the fourth invention of the present disclosure using an extrusion molding machine, etc. The molded article molded using the pellets according to the present disclosure exhibits good physical properties, particularly good mechanical properties.
[0278] <Tensile strength> Preferably, a molded article produced by the method described below in accordance with ISO 527 exhibits a tensile strength of 90 MPa or more, particularly preferably 92 MPa to 110 MPa, or 95 MPa to 100 MPa.
[0279] <Bending strength> Preferably, a molded article produced by the method described below in accordance with ISO178 exhibits a bending strength of 140 MPa or more, particularly preferably 140 MPa to 160 MPa, 140 MPa to 150 MPa, or 140 MPa to 145 MPa.
[0280] <Flexural modulus> Preferably, a molded article produced by the method described below in accordance with ISO178 exhibits a flexural modulus of 7100 MPa or more, particularly preferably 7100 MPa to 8000 MPa, 7100 MPa to 7500 MPa, or 7100 MPa to 7400 MPa.
[0281] The molded products used for evaluating tensile strength, flexural strength, and flexural modulus can be produced by molding the pellets to be evaluated into dumbbell pieces measuring 170 mm in length, 10 mm in width, and 4 mm in thickness using an injection molding machine (cylinder temperature 300°C, mold temperature 100°C). EXAMPLES
[0282] The invention according to the present disclosure will be described in more detail below by way of illustrative examples, but the invention is not limited to the following examples.
[0283] (First aspect of the present invention) <<Examples 1-1 to 1-3 according to the first aspect of the present invention and Comparative Example 1-1>> In Examples 1-1 to 1-3 according to the first aspect of the present invention and Comparative Example 1-1, a carbon fiber reinforced plastic (CFRP) plate as a plastic-containing material was heat-treated, and the plastic decomposition efficiency was evaluated.
[0284] <Example 1-1> Example 1-1 was carried out as follows.
[0285] (Provision and arrangement of materials) The semiconductor material is a chromium oxide (Cr) substrate on the surface of a honeycomb structure. 2 O 3 The carrier had a honeycomb structure and had 13 cells / 25 mm.
[0286] As the plastic-containing material, a CFRP plate with an epoxy resin content of 41% by weight was used.
[0287] The furnace volume was 9 L. Inside the furnace, a CFRP plate was placed on a support carrying chromium oxide as a semiconductor material. The support and the CFRP plate were placed in contact with each other.
[0288] The surface temperature of the CFRP plate was measured using a sensor placed within 5 mm from the surface of the CFRP plate.
[0289] (Heat treatment) The inner temperature of the furnace was increased by controlling the inner temperature of the furnace via the heater output of the furnace.
[0290] Before the surface temperature of the CFRP plate reached 300°C, a mixed gas of air and nitrogen gas with an oxygen concentration of 6% by volume was introduced into the heating furnace. The mixed gas was introduced into the heating furnace by sucking in the gas at a rate of 70 L / min from a suction port installed in the upper part of the heating furnace and letting the mixed gas flow in from a gas supply port installed in the lower part of the heating furnace. The oxygen concentration inside the heating furnace was measured with an oxygen monitor.
[0291] The heat treatment was carried out for 30 minutes in an atmosphere in which the oxygen concentration was controlled to 6 volume % by introducing the above mixed gas. During the heat treatment, the heater output of the heating furnace was adjusted to increase the surface temperature of the CFRP plate to a first surface temperature of 376°C.
[0292] (evaluation) The plastic decomposition efficiency in the method according to Example 1-1 was evaluated by calculating the weight reduction rate (wt%) from the difference between the weight of the CFRP plate before the heat treatment and the weight of the CFRP plate after the heat treatment. The results are shown in Table 1.
[0293] <Example 1-2> The heat treatment and evaluation of Example 1-2 were carried out in the same manner as Example 1-1, except that the carrier and the CFRP plate were placed 30 mm apart in the heating furnace, and the surface temperature of the CFRP plate was raised to 377° C. during the heat treatment. The results are shown in Table 1.
[0294] <Example 1-3> The heat treatment and evaluation of Example 1-3 were carried out in the same manner as in Example 1-1, except that the heat treatment time was 60 minutes and the surface temperature of the CFRP plate was raised to 371° C. during the heat treatment. The results are shown in Table 1.
[0295] <Comparative Example 1-1> The heat treatment and evaluation of Comparative Example 1-1 were carried out in the same manner as in Example 1-1, except that no semiconductor material was used and that the surface temperature of the CFRP plate was raised to 370° C. during the heat treatment. The results are shown in Table 1.
[0296] [Table 1]
[0297] As can be seen in Table 1, Examples 1-1 to 1-3, which were heated to a surface temperature of 371°C to 377°C in the presence of semiconductor material and with the introduction of a low-oxygen concentration gas with an oxygen concentration of 6% by volume, had a higher decomposition efficiency of plastic-containing materials than Comparative Example 1-1, which did not use semiconductor material.
[0298] In Example 1-3, the treatment time was extended to 60 minutes, but the increase in the weight loss rate was limited compared to Example 1-1, in which the treatment time was 30 minutes. This is believed to be because the sample surface was covered with carbides during the heat treatment, resulting in a decrease in the decomposition efficiency.
[0299] <<Examples 1-4 and Comparative Examples 1-2 according to the first aspect of the present invention>> <Example 1-4> The treatment and evaluation of Example 1-4 were carried out in the same manner as in Example 1-1, except that heating was carried out for 60 minutes at a surface temperature of 500° C. The results are shown in Table 2 below.
[0300] <Comparative Example 1-2> The treatment and evaluation of Comparative Example 1-2 were carried out in the same manner as in Example 1-4, except that no semiconductor material was used. The results are shown in Table 2 below.
[0301] [Table 2]
[0302] Photographs of the samples after the treatments according to Examples 1-4 and Comparative Examples 1-2 are shown in Figures 4 and 5, respectively, and Figure 3 shows a photograph of the sample before the treatments.
[0303] As can be seen in Table 2, Example 1-4, in which heat treatment was performed under semiconductor material with the introduction of low-oxygen concentration gas with an oxygen concentration of 6% by volume, showed a higher plastic decomposition efficiency than Comparison Example 1-2, in which heat treatment was performed without semiconductor material with the introduction of low-oxygen concentration gas with an oxygen concentration of 6% by volume.
[0304] Furthermore, as can be seen in FIG. 5, clumps of residual carbon derived from plastic were found adhering to the surface of the treated sample of Comparative Example 1-2, whereas, as can be seen in FIG. 4, no such residual carbon was found adhering to the treated sample of Example 1-4, and the treated sample had a relatively smooth and highly uniform surface, similar to the surface of the untreated sample shown in FIG. 3.
[0305] <<Examples 1-5 to 1-9 according to the first aspect of the present invention>> In Examples 1-5 to 1-9, a two-stage heat treatment was performed on a CFRP plate or a pressure vessel as a plastic-containing material. Then, the decomposition efficiency was evaluated, and the physical properties of the carbon fiber (carbon fiber material) obtained by the heat treatment were evaluated.
[0306] <Example 1-5> Examples 1-5 were carried out as follows.
[0307] (Provision and arrangement of materials) The semiconductor material is a chromium oxide (Cr) substrate on the surface of a honeycomb structure. 2 O 3 The carrier had a honeycomb structure and had 13 cells / 25 mm.
[0308] As the plastic-containing material, a CFRP plate with an epoxy resin content of 41% by weight was used. The physical properties of the carbon fibers contained in the CFRP plate before treatment are shown in Table 3 as Reference Example 1-1.
[0309] The furnace volume is 0.0525m 3 Inside the heating furnace, a CFRP plate was placed on top of a carrier carrying chromium oxide as a semiconductor material. The carrier and the CFRP plate were placed in contact with each other.
[0310] The surface temperature of the CFRP plate was measured by a sensor placed within 5 mm from the surface of the CFRP plate.
[0311] (Heat treatment) The internal temperature of the heating furnace was increased by controlling the heater output of the heating furnace. Then, before the surface temperature of the CFRP plate reached 300°C, a mixed gas of air and nitrogen gas with an oxygen concentration of 8% by volume was introduced into the heating furnace. The mixed gas was introduced into the heating furnace by suctioning at a gas introduction rate of 190 L / min and flowing the mixed gas from a gas supply unit installed in the heating furnace.
[0312] In Example 1-5, as well as the following Examples 1-6 and Comparative Example 1-4, the oxygen concentration in the heating furnace was measured by an oxygen monitor installed in the heating furnace. For Examples 1-7 to 1-9, the oxygen concentration in the furnace was calculated based on the furnace volume and the amount of gas introduced.
[0313] When the surface temperature of the CFRP plate reached 300°C, the generation of decomposition gas was confirmed.
[0314] The heat treatment was carried out for 120 minutes in an atmosphere in which the oxygen concentration was controlled to 8 volume % by introducing the above mixed gas. During the heat treatment, the heater output of the heating furnace was adjusted to raise the surface temperature of the CFRP plate to a first surface temperature of 450°C.
[0315] (Secondary heat treatment) Then, while maintaining the gas suction pressure, the supply of nitrogen gas was stopped and only air was supplied, and after confirming that the oxygen concentration in the heating furnace had reached 10% by volume or more, further heat treatment was performed. During the 260-minute heat treatment, the surface temperature of the CFRP plate was raised to 500°C. The average oxygen concentration over the 260 minutes was 14% by volume, and the maximum oxygen concentration was 18% by volume.
[0316] In Example 1-5, 0.8 kg of CFRP plate was treated. The treatment amount relative to the furnace volume was 15.2 kg / m 3 It was.
[0317] (carbon residue amount) The amount of residual carbon derived from plastics in the carbon fibers (recycled carbon fibers) recovered after the heat treatment was determined by thermogravimetric analysis. The value of the amount of residual carbon in Table 3 below indicates the amount of residual carbon (wt%) relative to the carbon fiber.
[0318] Thermogravimetric analysis was performed as follows: (i) performing a thermogravimetric analysis on a sample piece of 1 to 4 mg obtained by pulverizing the recovered carbon fiber, the thermogravimetric analysis including steps of heating from room temperature to 100°C, holding at 100°C for 30 minutes, heating from 100°C to 400°C, and holding at 400°C, at an air supply rate of 0.2 L / min, a heating rate of 5°C / min, and a recording rate of 1 / 6 s, for a total of 300 minutes; (ii) In a graph plotting the weight loss rate against time, an inflection point in the slope was identified, and the amount of residual carbon was calculated by subtracting the weight loss rate during the holding period at 100°C from the weight loss rate value at that inflection point.
[0319] In addition, the carbon fibers recovered after the heat treatment were measured for single fiber diameter and single fiber tensile strength, and the Weibull shape coefficient was calculated.
[0320] (single fiber tensile strength) The single fiber tensile strength was measured according to JIS R7606 as follows: At least 30 single fibers are taken from the fiber bundle. The diameter of the single fiber is measured in a side image of the single fiber taken by a digital microscope, and the cross-sectional area is calculated. The sampled single fiber was fixed to a perforated mount using adhesive. The mount on which the single fiber was fixed was attached to a tensile tester, and a tensile test was performed with a test length of 10 mm and a strain rate of 1 mm / min to measure the tensile breaking stress. The tensile strength is calculated from the cross-sectional area and tensile breaking stress of the single fiber. The single fiber tensile strength was determined as the average of the tensile strengths of at least 30 single fibers.
[0321] (Weibull shape factor) The Weibull shape factor was calculated according to the following formula: lnln{1 / (1-F)}=m×lnσ+C (In the formula, F is the fracture probability obtained by the symmetric sample cumulative distribution method, σ is the single fiber tensile strength (MPa), m is the Weibull shape coefficient, and C is a constant.)
[0322] A Weibull plot was made using lnln{1 / (1-F)} and lnσ, and the Weibull shape factor m was calculated from the linear approximation slope.
[0323] The evaluation results for Examples 1-5 are shown in Table 3. The fiber single yarn diameter is the average of the diameters of single fibers measured as described above for at least 30 single fibers.
[0324] <Examples 1-6>
[0325] The treatment was carried out in the same manner as in Examples 1-5, except that a pressure vessel was used as the plastic-containing material, the mixed gas was aspirated at a gas introduction rate of 127 L / min, and the oxygen concentration, surface temperature, and heat treatment time were as shown in Table 3 below.
[0326] The pressure vessels treated in Examples 1-6 had an aluminum liner and 44 wt. % FRP (fiber reinforced plastic), which contained 31 wt. % reinforcing fibers and 13 wt. % epoxy resin. The reinforcing fibers were composed primarily of carbon fibers with a small amount of glass fibers. The pressure vessels had a volume of 2.0 L.
[0327] The amount of FRP treated in Example 1-6 was 0.47 kg. The amount of FRP treated relative to the furnace volume was 9.0 kg / m 3 It was.
[0328] The evaluation results of the plastic decomposition efficiency for Examples 1-6 and the evaluation results of the physical properties of the recovered carbon fibers are shown in Table 3. The average oxygen concentration over 180 minutes of secondary heat treatment was 18 volume %, and the maximum oxygen concentration was 20 volume %.
[0329] The physical properties of the carbon fibers contained in the pressure vessel before treatment are shown in Table 3 as Reference Example 1-2.
[0330] <Example 1-7> The furnace volume is 0.1435m 3 The heat treatment was carried out in the same manner as in Example 1-5, except that the temperature was 100° C., the mixed gas of superheated steam and air was introduced into the heating furnace at a gas introduction rate of 29 L / min, and the surface temperature and the heat treatment time were as shown in Table 3 below.
[0331] The internal temperature of the heating furnace and the surface temperature of the sample were controlled via the heater output of the heating furnace and the temperature of the superheated steam.
[0332] In Example 1-7, 1.0 kg of CFRP plate was treated. The treatment amount relative to the furnace volume was 7.0 kg / m 3 It was.
[0333] The evaluation results of the plastic decomposition efficiency for Examples 1-7 and the evaluation results of the physical properties of the recovered carbon fibers are shown in Table 3. In the secondary heat treatment, only air was forced into the furnace at 29 L / min.
[0334] <Example 1-8> The treatment was carried out in the same manner as in Examples 1-7, except that a pressure vessel was used as the plastic-containing material, and the surface temperature and the heat treatment time were as shown in Table 3 below.
[0335] The pressure vessel used in Examples 1-8 was the same as the pressure vessel used in Examples 1-6.
[0336] The amount of FRP treated in Example 1-8 was 0.47 kg. The amount of FRP treated relative to the furnace volume was 3.3 kg / m 3 It was.
[0337] The evaluation results of the plastic decomposition efficiency for Examples 1-8 and the evaluation results of the physical properties of the recovered carbon fibers are shown in Table 3. In the secondary heat treatment, only air was forced into the furnace at 29 L / min.
[0338] <Example 1-9> The furnace volume is 0.049m 3 The treatment was carried out in the same manner as in Example 1-7, except that the temperature was 100° C., the mixed gas of superheated steam and air was introduced into the heating furnace at a gas introduction rate of 25 L / min, and the surface temperature and the time of the heat treatment were as shown in Table 3 below.
[0339] In Example 1-9, a CFRP plate with an epoxy resin ratio of 38% was treated. The treatment amount relative to the furnace volume was 1.6 kg / m 3 It was.
[0340] The evaluation results of the plastic decomposition efficiency for Examples 1-9 and the evaluation results of the physical properties of the recovered carbon fibers are shown in Table 3. In the secondary heating treatment, while continuing to supply superheated steam, the amount of air was increased and gas with an oxygen concentration of 11% by volume was forced into the furnace at 38 L / min.
[0341] The physical properties of the carbon fibers contained in the above CFRP plate according to Example 1-9 before treatment are shown in Table 3 as Reference Example 1-3.
[0342] <Comparative Examples 1-3 according to the first aspect of the present invention> In Comparative Example 1-3, the materials were provided and arranged in the same manner as in Example 1-5, and then the internal temperature of the heating furnace was increased without adjusting the oxygen concentration of the atmosphere in the heating furnace.
[0343] As a result, with the heater output remaining at the time when the surface temperature of the CFRP plate reached 300° C., excessive self-heating occurred, and the surface temperature of the CFRP plate rose to 485° C. The results are shown in Table 3.
[0344] In Comparative Example 1-3, 0.8 kg of CFRP plate was treated. The treatment amount relative to the furnace volume was 15.2 kg / m 3It was.
[0345] <Comparative Examples 1-4 according to the first aspect of the present invention>
[0346] The treatment was carried out in the same manner as in Examples 1-6, except that no semiconductor material was used.
[0347] The amount of FRP treated in Comparative Example 1-4 was 0.47 kg. The amount of FRP treated relative to the furnace volume was 9.0 kg / m 3 It was.
[0348] Regarding Comparative Examples 1-4, the evaluation results of the physical properties of the recovered carbon fibers are shown in Table 3. The average oxygen concentration over 180 minutes of the secondary heat treatment was 18 volume %, and the maximum oxygen concentration was 20 volume %.
[0349] [Table 3]
[0350] As can be seen in Table 3, Examples 1-5 to 1-9, in which a low-oxygen concentration gas with an oxygen concentration of 6 to 8 volume % was introduced, a primary heat treatment was performed in the presence of semiconductor material, and then a secondary heat treatment was further performed under an elevated oxygen concentration, showed low residual carbon amounts (residual carbon component amounts) and very excellent plastic decomposition efficiency.
[0351] In addition, in Comparative Example 1-3 where the oxygen concentration was not controlled, excessive self-heating occurred, whereas in Examples 1-5 to 1-9 where a low-oxygen gas with an oxygen concentration of 6 to 8% by volume was introduced into the heating furnace, excessive self-heating was not observed. In Comparative Example 1-3, the oxygen concentration was excessive because the decomposition process was started without lowering the oxygen concentration in advance, and as a result, it is believed that the decomposition temperature could not be appropriately controlled in the presence of the semiconductor material.
[0352] Furthermore, the carbon fibers recovered in Examples 1-5 to 1-9 maintained approximately the same fiber single yarn diameter and single fiber tensile strength as the carbon fibers before treatment (Reference Examples 1-1 to 1-3), and the Weibull shape coefficient of single fiber tensile strength was higher. That is, in Examples 1-5 to 1-9, the recovered carbon fibers had better physical properties than the carbon fibers before producing carbon fiber reinforced plastic.
[0353] Furthermore, the carbon fibers recovered in Example 1-6, which involved heat treatment under a semiconductor material, had superior quality, particularly in terms of single fiber tensile strength and Weibull shape factor, to the carbon fibers recovered in Comparative Example 1-4, which involved heat treatment without a semiconductor material.
[0354] <<Example 2-1 according to the second aspect of the present invention>> <Material preparation> (Recycled Carbon Fiber) In Example 2-1, the recycled carbon fiber used was a recycled carbon fiber having an average length of 50 mm, an average single fiber diameter of 6.7 μm, a single fiber tensile strength of 4.7 GPa, a Weibull shape coefficient of 7.0, and a residual carbon content of 0.6% by weight, which was regenerated by a semiconductor thermal activation method using CFRP as raw material using the method according to the first invention of the present disclosure.
[0355] (single fiber tensile strength) The single fiber tensile strength was measured in accordance with JIS R7606 in the same manner as in Examples 1-5 above.
[0356] (Weibull shape factor) The Weibull shape coefficient was calculated in the same manner as in Examples 1-5 above.
[0357] (carbon residue amount) The amount of residual carbon in the recycled carbon fiber was determined by thermogravimetric analysis (TGA method) as follows: (i) A 4 mg sample piece obtained by pulverizing the recycled carbon fiber was subjected to a thermogravimetric analysis for a total of about 600 minutes, the analysis comprising steps of heating from room temperature to 100°C, holding at 100°C for 30 minutes, heating from 100°C to 400°C, and holding at 400°C for 480 minutes, at an air supply rate of 0.2 L / min, a heating rate of 5°C / min, and a recording rate of 1 / 6 s, in a thermogravimetric analyzer; (ii) In a graph plotting the weight loss rate against time, the inflection point of the slope was identified, and the amount of residual carbon was calculated by subtracting the weight loss rate during the holding period at 100°C from the weight loss rate value at that inflection point.
[0358] The above recycled carbon fiber was immersed in an aqueous dispersion of epoxy resin, removed, and then dried in a dryer. 2% by weight of epoxy resin was applied to the recycled carbon fiber as a binder with the thermoplastic resin.
[0359] (Thermoplastic resin fiber) In Example 2-1, polyamide 66 resin fibers having an average length of 38 mm (PA66 resin fibers (Toray Industries, Inc., 1401-1.3T-38 E9), single yarn fineness 1.3 dtex, crimp number 17 crimps / 25 mm, melting point 265° C.) were used as the thermoplastic resin fibers.
[0360] <Production of blended yarn> The recycled carbon fiber with the binder added was mixed in a ratio of 80% by weight and the PA66 resin fiber was mixed in a ratio of 20% by weight, and the resultant mixture was spun through the processes of carding, drawing, and roving to produce a continuous blended yarn (blended yarn according to Example 2-1) of 0.86 g / m. In the roving process, the yarn was twisted at 200 times / m.
[0361] <Production of carbon fiber reinforced thermoplastic resin pellets> Next, the blended yarn obtained above was coated with polyamide 6 (Akulon (registered trademark) F-X9182, melting point 220°C, manufactured by DSM) using a crosshead die for coating electric wire with an outlet diameter of 3 mm, and cut to a length of 3 mm to obtain core-sheath type pellets (carbon fiber reinforced thermoplastic resin pellets according to Example 2-1) suitable for injection molding, with a carbon fiber content of 17 mass% (463 mass parts of polyamide 6 per 100 mass parts of carbon fiber), a diameter of 2.6 mm, and a cut length of 3 mm.
[0362] <Injection molding evaluation> The obtained carbon fiber reinforced thermoplastic resin pellets were used as raw materials and injection molded using a 110 ton electric injection molding machine (manufactured by Japan Steel Works, J110AD) at cylinder temperatures C1 / C2 / C3 / C4 / N = 265°C / 270°C / 280°C / 280°C / 280°C (C1 to C4 are cavities, N is nozzle) with a molding cycle of 40 seconds to obtain a dumbbell for tensile test with a wall thickness of 4 mm (molded body according to Example 2-1). The obtained molded body had no lumps of fibrous material or bubbles due to poor dispersion, and had a good appearance.
[0363] The resulting dumbbell was used as a test piece and tensile strength was measured in accordance with ISO 527 (JIS K7161).The tensile strength was 200 MPa, indicating excellent mechanical properties.
[0364] The average fiber length of the recycled carbon fibers contained in the molded product was 0.33 mm.
[0365] The average fiber length of the recycled carbon fibers in the molded product was evaluated as follows: A test piece of 20 mm x 10 mm was cut out from the obtained molded body and heated at 550 ° C for 1.5 hours in an oxygen atmosphere to burn off the resin components. The remaining carbon fiber was put into water and thoroughly stirred with ultrasonic vibration. The stirred dispersion was randomly collected with a measuring spoon to obtain an evaluation sample. The length of 3,000 fibers was measured with a Nireco Corporation image analyzer Luzex AP, the average length was calculated, and the average fiber length of the carbon fiber in the molded body was obtained.
[0366] The results for Example 2-1 are shown in Table 4 below.
[0367] <Comparative Example 2-1 according to the second aspect of the present invention> Except for using recycled carbon fiber with a residual carbon content of 7.1% by weight, the same procedure as in Example 2-1 was used to manufacture a blended yarn. The single fiber tensile strength and Weibull shape coefficient of the recycled carbon fiber could not be evaluated because the single fibers were strongly bonded to each other by the residual carbon and it was not possible to separate and collect the single fibers.
[0368] In Comparative Example 2-1, it was observed that the bonds between the single fibers of the recycled carbon fiber were not sufficiently opened during the carding process, and the single fibers were not entangled sufficiently, and yarn loss occurred, so it was not possible to produce a continuous blended yarn. The results are shown in Table 4 below.
[0369] [Table 4]
[0370] <<Example 3-1 according to the third aspect of the present invention>> <Material preparation> (Recycled Carbon Fiber) The recycled carbon fibers used were those that had been regenerated by a semiconductor thermal activation method using CFRP as raw material according to the method of the first invention of the present disclosure, and had an average length of 50 mm, an average single fiber diameter of 6.7 μm, a single fiber tensile strength of 4.7 GPa, a Weibull shape coefficient of 7.0, and a residual carbon content of 0.6% by weight.
[0371] (single fiber tensile strength) The single fiber tensile strength was measured in accordance with JIS R7606 in the same manner as in Examples 1-5 above.
[0372] (Weibull shape factor) The Weibull shape coefficient was calculated in the same manner as in Examples 1-5 above.
[0373] (carbon residue amount) The amount of residual carbon in the recycled carbon fibers was determined by thermogravimetric analysis (TGA method) in the same manner as in Example 2-1 above.
[0374] The above recycled carbon fibers were immersed in an aqueous dispersion of epoxy resin, then removed and dried in a dryer. 2% by weight of epoxy resin was applied to the recycled carbon fibers as a binder with the thermoplastic resin.
[0375] (Thermoplastic resin fiber) As the thermoplastic resin fiber, polyamide 66 resin fiber (PA66 resin fiber (Toray Industries, Inc., 1401-1.3T-38 E9), single yarn fineness 1.3 dtex, crimp number 17 crimps / 25 mm, melting point 265° C.) having an average length of 38 mm was used.
[0376] <Production of blended yarn> By mixing 80% by weight of recycled carbon fiber with binder and 20% by weight of PA66 resin fiber, and then carding, drawing, and roving processes, a continuous blended yarn of 0.86 g / m was produced. The roving process involved twisting the yarn 200 times / m.
[0377] <Production of carbon fiber reinforced thermoplastic resin strands> Next, the blended yarn obtained above was coated with polyamide 6 (Akulon (registered trademark) F-X9182, melting point 220°C, manufactured by DSM) using a crosshead die for coating electric wire with an outlet diameter of 2.3 mm, and this was wound up with a winder to obtain a strand-shaped fiber-reinforced plastic (carbon fiber-reinforced thermoplastic resin strand according to Example 3-1) having a core-sheath structure with a carbon fiber content of 17 mass% (463 mass parts of polyamide 6 per 100 mass parts of carbon fiber) and an average diameter of 2.0 mm.
[0378] <Modeling using 3D printing equipment> The above-mentioned strand-shaped fiber-reinforced plastic with an average diameter of 2.0 mm was set in a fused deposition modeling device ("BS01" manufactured by Bonsai Lab Co., Ltd.) and a modeling test was conducted under the following conditions at a discharge head temperature of 280°C. Discharge head movement speed: 30mm / min (when discharging resin), 130mm / min (when discharging stops). Discharge amount (magnification): 100% Layer pitch: 0.2mm Laminated bed temperature: 25℃ Ambient temperature: 25℃ Ambient relative humidity: 40% During printing, no fans or blowers were used to cool the model.
[0379] (1) Sag rating: Two cubes with sides of 10 mm were used as bridge girders, which were placed parallel to each other on a horizontal plane with a center-to-center distance of 50 mm, and a plate with a length of 60 mm, width of 10 mm, and thickness of 0.2 mm was placed on top of them. A 3D model of a bridge shape was designed using 3D CAD, and this model was printed under the above conditions to produce a 3D model. The distance Z between the plate-like part of the printed 3D model and the part closest to the stacked bed was measured, and the amount of sagging was calculated using the following formula. Droop amount (mm) = 10-Z The molding was repeated three times to calculate the average amount of sagging, and an average value of 0 mm or more and less than 2 mm was rated as excellent (◎), 2 mm or more and less than 4 mm was rated as pass (○), and 4 mm or more was rated as fail (×). When the obtained strands were evaluated for sagging, the average amount of sagging was 3.4 mm.
[0380] (2) Evaluation of discharge / stop response: A three-dimensional model was designed using three-dimensional CAD, in which 25 rectangular columns with a cross section of 2 mm on each side and a height of 20 mm were arranged on a 5 × 5 square lattice drawn at 10 mm intervals on a horizontal plane, and this model was molded under the above conditions to produce a three-dimensional object. The dimensions of the molded three-dimensional model were measured with a vernier caliper, and the number of rectangular columns with two sides of the cross section that were 3 mm or more was determined as the number of molding failures. The molding was repeated three times to calculate the average number of molding failures, and an average of 0 to less than 2 was determined as excellent (◎), 2 to less than 5 was determined as pass (○), and 5 or more was determined as fail (×). When the discharge / stop responsiveness of the obtained strand was evaluated, the average number of molding failures was 3.7.
[0381] (3) Evaluation of model stability: A three-dimensional model was designed using three-dimensional CAD, in which 25 rectangular columns with a cross section of 10 mm and a height of 100 mm were arranged upright on a 5 × 5 square lattice drawn at 20 mm intervals on a horizontal plane, and this model was molded under the above conditions to produce a three-dimensional object. The strand used for the molding weighed 300 g (volume 250 cm). 3 The strands used were ones that were well over the limit of 104 m (continuous length). If the molding was completed without any problems, it was rated as passed (○), and if the amount of discharge decreased or discharge stopped midway, it was rated as failed (×). An evaluation of the molding stability of the obtained strands was carried out, and the molding was completed without any problems.
[0382] The results for Example 3-1 are shown in Table 5 below.
[0383] <Comparative Example 3-1 according to the third aspect of the present invention> Except for using recycled carbon fiber with a residual carbon content of 7.1% by weight, the same procedure as in Example 3-1 was used to manufacture a blended yarn. Note that it was difficult to measure the single fiber tensile strength and Weibull shape coefficient of the recycled carbon fiber because the single fibers were strongly bonded to each other by the residual carbon.
[0384] In Comparative Example 3-1, it was observed that the bonds between the single fibers of the recycled carbon fiber were not sufficiently opened during the carding process, and the single fibers were not entangled sufficiently, and yarn loss occurred, so it was not possible to produce a continuous blended yarn. The results are shown in Table 5 below.
[0385] [Table 5] [Explanation of symbols]
[0386] 11 Semiconductor Materials 12 Plastic-containing materials 20 Furnace 21 Carrier having semiconductor material 22 Plastic-containing materials 23 Heat source (heater) 24 Gas Supply Section 25 Exhaust port 26 Furnace interior space 27 Temperature Sensor 100 Carbon Fiber Reinforced Thermoplastic Strands 110 Strand core component 120 Strand sheath components 200 Carbon fiber reinforced thermoplastic resin pellets 210 Pellet core components 220 Pellet sheath components L Pellet cut length R Pellet diameter C. Disconnection process 100b Carbon fiber reinforced thermoplastic resin strand according to the present disclosure 110b Core component 120b Sheath component
Claims
1. Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of 2% by volume or more and less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; Including, The plastic-containing material and the semiconductor material are spaced apart from each other by a distance of 50 mm or less. Method for decomposing plastic-containing materials.
2. 2. The method of claim 1, wherein the low oxygen concentration gas is introduced into the atmosphere of the furnace while the surface temperature of the plastic-containing material is below 300°C.
3. The decomposition method according to claim 1 or 2, wherein the first surface temperature is 300°C to 600°C.
4. The decomposition method according to any one of claims 1 to 3, wherein the low oxygen concentration gas is a mixed gas of air and a diluent gas.
5. The decomposition method according to any one of claims 1 to 4, comprising heating the plastic-containing material subjected to the heat treatment at the first surface temperature in an atmosphere having an oxygen concentration of 10% by volume or more in the presence of a semiconductor material.
6. The plastic-containing material contains a plastic and an inorganic material; and The method includes decomposing the plastic in the plastic-containing material by the decomposition method according to any one of claims 1 to 5, and recovering the inorganic material. Methods for recovering inorganic materials.
7. 7. The method of claim 6, wherein the residual carbon from the plastic recovered together with the inorganic material is 5% or less by weight of the inorganic material.
8. 8. The method according to claim 6 or 7, wherein the plastic-containing material is a carbon fiber reinforced plastic containing carbon fiber as the inorganic material.
9. 9. The method of claim 8, wherein the recovered carbon fibers have a single fiber tensile strength of 3.0 GPa or greater and a Weibull shape factor of 6.0 or greater.
10. Heating the plastic-containing material to a first surface temperature in an atmosphere in a heating furnace into which a low-oxygen concentration gas having an oxygen concentration of 2% by volume or more and less than 10% by volume has been introduced, in the presence of a semiconductor material, to decompose the plastic in the plastic-containing material; Including, Here, the plastic-containing material is a carbon fiber reinforced plastic containing carbon fiber. A method for producing recycled carbon fibers having a single fiber tensile strength of 3.0 GPa or more and a Weibull shape coefficient of 6.0 or more.
Citation Information
Patent Citations
Manufacture of composite body
JP1988087228A
A blended yarn as a thermoplastic matrix composite material and method for its manufacture
JP1990112427A
Method for carrying out thermal decomposition treatment of carbon fiber reinforced composite material
JP1994298993A
Method for decomposing compound
JP2005139440A
Method for pyrolyzing waste plastic
JP2005307007A